Composite conductor comprising radiation coating and / or hard coating and method for producing same
Coated conductors with low solar absorptivity and high emissivity coatings address temperature limitations and material degradation, improving current carrying capacity and safety in power transmission systems.
Patent Information
- Application Number
- CN202380040426.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-03-24
- Publication Date
- 2024-12-31
AI Technical Summary
The current electrical conductors used in power transmission and distribution systems are limited by their current carrying capacity due to high operating temperatures, which are exacerbated by solar radiation absorption and material degradation, leading to inefficiencies and safety hazards.
Coated conductors with a composite core and encapsulation layer featuring low solar absorptivity and high radiative emissivity coatings, along with optional high corrosion and erosion resistance, to reduce operating temperatures and enhance current carrying capacity.
The coatings effectively lower conductor temperatures, increase current carrying capacity, and improve safety by reducing material degradation and reflectivity-related hazards, thereby enhancing the performance and reliability of power transmission systems.
Smart Images

Figure CN119234282A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 324,468, filed on March 28, 2022, entitled “Composite Conductors Including Radiative Coatings and Methods of Manufacture Thereof,” and U.S. Provisional Application No. 63 / 353,390, filed on June 17, 2022, entitled “Composite Conductors Including Radiative and / or Hard Coatings and Methods of Manufacture Thereof,” and the entire disclosures of the above applications are incorporated herein by reference. Technical Field
[0003]
[0013] Embodiments described herein generally relate to conductors used in grid power transmission and distribution applications. Background Art
[0004] The electrical grid is a major contributor to greenhouse gas emissions and global warming. The U.S. electrical grid is more than 25 years old, and approximately 2,000 TWh of electricity is wasted worldwide each year, and compensatory power generation alone is associated with approximately 1 billion metric tons of GHG emissions. As the demand for electricity grows, the need for higher capacity transmission and distribution lines is also increasing. The amount of electricity carried by electrical conductors depends on the current carrying capacity (also known as the ampacity) of the conductors that transmit the current. However, the current carrying capacity of such conductors is limited by the operating temperature of the conductors and the line sag. Excessive temperatures not only increase line sag, but can also damage the conductors or other components of the transmission system. The inherent resistance of the conductor causes the conductor to generate heat, further increasing the operating temperature of the conductor. In addition, since the conductors are typically formed of metallic materials, conductors used for power grid transmission and distribution are good absorbers of solar radiation. The absorption of solar radiation also increases the operating temperature of such conductors, which further increases the operating temperature of the conductors and reduces the current carrying capacity of the electrical conductors. In addition, many conductors are formed of aluminum or other soft materials that are easily cut or corroded, resulting in accidents and loss of service. Summary of the invention
[0005] Embodiments described herein generally relate to power transmission systems and methods using coated conductors, and in particular to electrical conductors comprising a strength member and a conductor layer, the strength member comprising a composite core and an encapsulation layer disposed around the composite core, the conductor layer comprising a plurality of strands of conductive material disposed around the strength member. A coating having low solar absorptivity and high radiative emissivity is disposed around at least a surface layer of the conductor to reduce the solar absorptivity of the conductor and / or increase the radiative emissivity of the conductor, thereby reducing the operating temperature of the conductor when transmitting a specific current, or increasing the current carrying capacity of the conductor at a specific operating temperature relative to an uncoated conductor. The reduced operating temperature also reduces the conductor resistance and associated line losses in the power grid. In addition, the coating may have a high corrosion resistance to prevent accidental cutting of the conductor layer, such as shearing by a kite line. Furthermore, the encapsulation layer may additionally or alternatively be configured to have a high reflectivity, and / or the outer surface of the conductor layer may be configured to have a low reflectivity. Embodiments described herein are also applicable to power distribution at low voltages, such as operating voltages below 69 kV. The coatings described herein may be configured to include any combination of properties and / or functionality described herein, including but not limited to reduced solar absorptivity, increased radiant emissivity, and / or improved erosion or corrosion resistance of a conductor.
[0006] In some embodiments, a device includes a strength member, the strength member including a core formed of a composite material and an encapsulation layer disposed around the core. A conductor layer is disposed around the strength member. A coating is disposed on the conductor layer. The coating is formulated to have an absorptivity of less than 0.5 at a wavelength less than 2.5 microns and a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60°C to 250°C.
[0007] In some embodiments, a device includes a strength member, the strength member including a core formed of a composite material and an encapsulation layer arranged around the core. The outer surface of the encapsulation layer is configured to have a reflectivity greater than 50% at a thermal radiation wavelength corresponding to an operating temperature greater than 90°C. In some embodiments, the outer surface is treated to have a reflectivity greater than 50%. In some embodiments, the outer surface is coated with a coating having a reflectivity greater than 50%. In some embodiments, a conductor layer is optionally arranged around the strength member.
[0008] In some embodiments, an apparatus includes a strength member comprising:
[0009] A core formed of a composite material and an encapsulation layer disposed around the core. A conductor layer is disposed around the strength member. A coating is disposed on the conductor layer. The coating is formulated to have a corrosion resistance at least 5% higher than the corrosion resistance of aluminum or an aluminum alloy.
[0010] In some embodiments, an assembly includes a conductor, the conductor including: a strength member and a conductor layer, the strength member including a core formed of a composite material and an encapsulation layer arranged around the core; the conductor layer is arranged around the strength member. A coupler is coupled to an axial end of the conductor. A coating is arranged on an outer surface of the coupler, the coating being formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns and / or a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60°C to 250°C.
[0011] It should be appreciated that all combinations of the above concepts and the additional concepts discussed in more detail below (as long as such concepts are not mutually inconsistent) are considered to be part of the inventive subject matter disclosed herein. In particular, all combinations of the claimed subject matter appearing at the end of this disclosure are considered to be part of the inventive subject matter disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The above and other features of the present disclosure will become more apparent from the following description and the appended claims in conjunction with the accompanying drawings. It is to be understood that these drawings depict only several implementations according to the present disclosure and should not be considered as limiting the scope thereof, and the present disclosure will be described in additional detail and detail through the use of the accompanying drawings.
[0013] Figure 1 It is a schematic diagram of a conductor used in power grid transmission according to an embodiment, the conductor comprising an outer coating arranged on a conductor layer of the conductor, the outer coating having low solar absorptivity and high radiation emissivity, and may also have high erosion resistance and high corrosion resistance, and the conductor may optionally include an inner coating having high reflectivity coated on a strength member of the conductor.
[0014] Figure 2 is a side cross-sectional view of a conductor including an outer coating according to an embodiment.
[0015] Figure 3 is a side cross-sectional view of a conductor including an outer coating and an inner coating according to an embodiment.
[0016] Figure 4 is a schematic diagram of a coating having low solar absorptivity and high radiation emissivity for coating on a conductor according to an embodiment. Such a coating on a conductor may also optionally have high corrosion resistance.
[0017] Figure 5 is a schematic diagram of a multi-layer coating having low solar absorptivity and high radiant emissivity for coating on a conductor according to an embodiment, the multi-layer coating may optionally include an additional layer having high corrosion resistance.
[0018] Fig. 6A is a side cross-sectional view of a coupler crimped to an axial end of a strength member of a conductor and coated with a coating having low solar absorptivity and high radiant emissivity and optionally high erosion and corrosion resistance in accordance with an embodiment.
[0019] Figure 6B is a side cross-sectional view of a coupler crimped to the axial ends of a strength member of two conductors to splice the two conductors together and coated with a coating having low solar absorptivity and high radiant emissivity, and optionally high corrosion resistance, in accordance with an embodiment.
[0020] Figure 7 is a schematic flow chart of a method according to an embodiment, which is used to prepare a conductor including a strength member and a conductor layer, and reduce the solar absorptivity and increase the radiant emissivity of the conductor by arranging a coating with low solar absorptivity, high radiant emissivity and optionally high corrosion resistance on the conductor.
[0021] The following detailed description refers to the accompanying drawings throughout. In the drawings, similar symbols generally identify similar components unless the context indicates otherwise. The illustrative implementations described in the detailed description, drawings, and claims are not meant to be limiting. Other implementations may be utilized, and other changes may be made, without departing from the spirit or scope of the subject matter presented herein. It is readily understood that the various aspects of the present disclosure as generally described herein and illustrated in the accompanying drawings may be arranged, substituted, combined, and designed in a variety of different configurations, all of which are expressly contemplated and become part of the present disclosure. DETAILED DESCRIPTION
[0022] Embodiments described herein generally relate to power transmission and distribution systems and methods using coated conductors or conductor surface modifications, and more particularly to electrical conductors including a strength member and a conductor layer, the strength member including a composite core and an encapsulation layer disposed about the composite core, the conductor layer including a plurality of strands of conductive material disposed (e.g., wound or twisted) about the strength member. A coating having a low solar absorptivity and a high radiant emissivity is disposed about at least the conductor layer to reduce the solar absorptivity of the conductor and increase the radiant emissivity of the conductor, thereby reducing the operating temperature of the conductor when transmitting a specific current and / or increasing the current carrying capacity of the conductor at a specific operating temperature relative to an uncoated conductor. The reduced operating temperature also reduces conductor resistance and associated line losses in an electrical grid.
[0023] In addition, the coating may also have high corrosion resistance to prevent accidental cutting of the conductor layer, such as shearing by a kite line. In addition, the encapsulation layer may be additionally or alternatively configured to have a high reflectivity, and / or the outer surface of the conductor layer may be configured to have a low reflectivity. The embodiments described herein are applicable to conductors having strength members including a composite material but without encapsulation, or having strength members that do not include a composite material, for example, strength members including steel strands, or aluminum or aluminum alloy strands in the conductor. The embodiments described herein are also applicable to power distribution at low voltages such as operating voltages below 69 kV. The coatings described herein may be configured to include any combination of the properties and / or functions described herein, including but not limited to reduced solar absorptivity, increased radiation emissivity, and / or improved corrosion resistance or corrosion resistance of the conductor. Any strength member described herein may be a metal or fiber-reinforced inorganic or metal-based composite material, and may be insulating or conductive.
[0024] As the demand for electricity grows, the need for higher capacity transmission and distribution lines is also increasing. The amount of electricity that can be carried by an electrical conductor depends on the current carrying capacity of the conductor that is carrying the current. However, the current carrying capacity of such a conductor is limited by the operating temperature of the conductor. Excessive temperatures can damage the conductor or other components of the grid system. The inherent resistance of the conductor causes the conductor to generate heat, further increasing the operating temperature of the conductor. In addition, since the conductor is usually formed of metallic materials, the conductors used for grid transmission and distribution are good absorbers of solar radiation. For example, the solar radiation incident on overhead wires can reach 1000W / ft 2 The absorption of solar radiation also increases the operating temperature of such conductors, thereby further increasing the operating temperature of the conductors and reducing the current carrying capacity of the electrical conductors.
[0025] The amount of solar radiation absorbed by a conductor depends on the absorptivity ("solar absorptivity") coefficient of the conductor surface, with a low absorptivity indicating that the conductor absorbs only a small amount of solar radiation. In addition, the conductor can dissipate heat by conduction, convection, or radiation (e.g., emitting heat in the form of photons). The amount of heat radiated by a conductor to the environment depends on the emissivity ("radiative emissivity") coefficient of the conductor surface, with a high radiative emissivity indicating that the conductor emits more heat relative to a conductor with a low radiative emissivity.
[0026] Additionally, many conductors are made of soft materials such as aluminum, which are susceptible to erosion and cutting. For example, kite flying is a common recreational activity in countries such as Brazil, India, and Pakistan. While kite strings are typically made of fabric, many kite flyers use strings filled with glass shavings or metal filings, or use metal wire to fly their kites. Such strings can cut through the insulating sheath that is sometimes arranged around the conductor strands, which can cause electric shock to the kite flyer if such strings include conductive materials. In addition, such strings can also cut through the conductor layer, thereby severing the conductor, which can cause live wires to fall, also posing a risk of electric shock and leading to interruptions in power transmission. In Brazil alone, 30 kite-cutting-related accidents have been reported in the past seven years, including five deaths in 2020. Similar incidents have also been reported in India and Pakistan.
[0027] Some conductors have a shiny outer conductor layer which makes them highly reflective. This is undesirable because the light reflected from such electrical conductors can distract drivers travelling on the road near such conductors or cause them to have their vision impaired. This can be a serious safety hazard and can lead to accidents.
[0028] Embodiments of the conductor described herein include a strength member and a conductor layer disposed around the strength member, and include a low solar absorptivity and high radiant emissivity coating disposed around the conductor layer, which coating may additionally or alternatively also have sufficient hardness to have substantial erosion or cut resistance, and optionally, also include a highly reflective surface treatment around the strength member, these embodiments can provide one or more benefits, including, for example: 1) reducing solar absorption and increasing radiant emission from the conductor layer included in the conductor, thereby enabling the conductor to operate at a lower temperature, or conduct a greater amount of current (i.e., have a greater current carrying capacity) at the same operating temperature; 2) reducing heat absorption of the strength member by additionally providing a low absorptivity or high reflectivity surface treatment on the strength member, thereby reducing the strength member at 1) protecting the conductor surface from scratches, thereby reducing the corona effect, providing UV resistance, and improving durability; 2) inhibiting cutting and / or erosion of the conductor by kite lines or other environmental factors, thereby improving safety and reducing transmission losses; 3) protecting the conductor surface from scratches, thereby reducing the corona effect, providing UV resistance, and improving durability; 4) inhibiting cutting and / or erosion of the conductor by kite lines or other environmental factors, thereby improving safety and reducing transmission losses; 5) protecting the composite core of the strength member from moisture and / or solvents that may damage the composite core; 6) enhancing the reflectivity of the encapsulation layer of the composite core of the conductor, thereby reducing heat transfer to the composite core, allowing the conductor to operate at higher temperatures; 7) reducing the reflectivity of the outer conductor layer of the conductor, thereby improving road safety by reducing reflections from such conductors that may affect driver visibility; and 8) improving the performance of the conductor without affecting the functionality, reliability and / or performance of the conductor.
[0029] Figure 1 1 is a schematic diagram of a conductor 100 according to an embodiment. The conductor 100 includes a strength member 110 , a conductor layer 120 disposed around the strength member 110 , and an outer coating 130 disposed around the conductor layer 120 .
[0030] The strength member 110 includes a core 112 and an encapsulation layer 114 arranged around the core 112 (e.g., arranged circumferentially around the core 112). The core 112 can be formed of a composite material. In some embodiments, the composite material can include a non-metallic fiber-reinforced metal matrix composite material, a carbon fiber-reinforced composite material with a thermoplastic or thermosetting matrix or even a metal matrix, or a composite material reinforced with other types of fibers such as quartz, AR glass, E glass, S glass, H glass, silicon carbide, silicon nitride, aluminum oxide, basalt fiber, specially formulated silica fiber, any other suitable composite material or any combination thereof. In some embodiments, the composite material includes a carbon fiber-reinforced composite material of a thermoplastic or thermosetting resin. The reinforcement in the composite strength member can be discontinuous, such as whiskers or chopped fibers; or continuous fibers in a substantially aligned configuration (e.g., parallel to the axial direction) or randomly dispersed (including a spirally wound or interwoven configuration). In some embodiments, the composite material may include a continuous or discontinuous polymer-based composite material reinforced by carbon fiber, glass fiber, quartz, ceramic fiber such as alumina fiber, or other reinforcing material, and may also include fillers or additives (e.g., nano additives). In some embodiments, the core 112 may include a carbon composite material including a polymer matrix of an epoxy resin cured with an anhydride curing agent.
[0031] The core 112 may have any suitable cross-sectional width (e.g., diameter). In some embodiments, the core 112 has a diameter in the range of about 2 mm (inclusive) to about 15 mm (inclusive) (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 mm (inclusive)). In some embodiments, the core 112 may have a diameter in the range of about 5 mm (inclusive) to about 10 mm (inclusive). In some embodiments, the core 112 may have a diameter in the range of about 10 mm (inclusive) to about 15 mm (inclusive). In some embodiments, the core 112 may have a diameter in the range of about 7 mm (inclusive) to about 12 mm (inclusive). In some embodiments, the core 112 may have a diameter of about 9 mm. In some embodiments, the core 112 can have a glass transition temperature (e.g., for thermoset composites) or melting point of at least about 70° C. (e.g., at least 75° C., at least 80° C., at least 90° C., at least 100° C., at least 120° C., at least 140° C., at least 150° C., at least 160° C., at least 180° C., at least 200° C., at least 220° C., at least 240° C., or at least 250° C., inclusive). The glass transition temperature or melting point of the core 112 can correspond to a threshold operating temperature of the conductor 100, which can limit the current carrying capacity of the conductor 100. In other words, the maximum amount of current that can be carried by the conductor 100 is the current at which the operating temperature of the conductor 100, or at least the temperature of the core 112, is below the glass transition temperature or melting point of the composite core 112.
[0032] In some embodiments, the core 112 defines a circular cross-section. In some embodiments, the core 112 can define an oval, elliptical, polygonal, or asymmetric cross-section. In some embodiments, the strength member 110 can include a single core 112. In other embodiments, the strength member 110 can include multiple cores, such as 2, 3, 4, or even more, with an encapsulation layer 114 arranged around the multiple cores or around each individual core. In such embodiments, each of the multiple cores can be substantially similar to each other, or at least one of the multiple cores can be different from the other cores (e.g., having a different size, a different shape, formed of a different material, having components embedded therein, etc.).
[0033] In some embodiments, the core 112 is solid, i.e., does not include any holes or voids therein except for trace amounts of naturally occurring voids or pores that may be formed during the manufacturing process of the core 112. In some embodiments, the core 112 may be hollow, e.g., one or more intentionally formed channels or voids are defined therein or therethrough (e.g., extending axially along the longitudinal axis of the strength member 110 and / or defined around the longitudinal axis of the strength member 110). Sensing or transmission components may be embedded in the voids or channels defined in the core 112. For example, in some embodiments, sensors such as strain gauges, accelerometers, or fiber optic sensors may be disposed within or throughout the core 112. The sensors may be configured to sense various operating parameters of the conductor 100, such as mechanical strain, sag (i.e., the vertical difference between the support point of the conductor 100 and the lowest point of the conductor 100), operating temperature, voltage or current through the conductor 100, any other suitable operating parameter, or combinations thereof. In some embodiments, the optical fiber extending through the core 112 may include a communication optical fiber. In such an embodiment, the optical fiber may transmit optical signals therethrough (eg, transmitting sensor data, Internet or media signals, etc.).
[0034] The encapsulation layer 114 is arranged around the core 112, for example, circumferentially around the core 112. In some embodiments, an inner insulating layer (not shown) may be optionally inserted between the core 112 and the encapsulation layer 114. The inner insulating layer may be formed of any suitable insulating material, for example, glass fibers (glass arranged substantially parallel to the axial direction or interwoven or braided), a resin layer, an insulating coating, any other suitable insulating material, or a combination thereof. In some embodiments, the inner insulating layer may also be arranged on the axial ends of the core 112, for example, to protect the axial ends of the core 112 from corrosive chemicals, environmental damage, etc.
[0035] The encapsulation layer 114 may be formed of any suitable conductive or non-conductive material. In some embodiments, the encapsulation layer 114 may be formed of a conductive material including, but not limited to, aluminum (e.g., 1350-H19), annealed aluminum (e.g., 1350-0), aluminum alloys (e.g., Al-Zr alloys, 6000 series aluminum alloys such as 6201-TS1, -T82, -T83, 7000 series aluminum alloys, 8000 series aluminum alloys, etc.), copper, copper alloys (e.g., copper-magnesium alloys, copper-tin alloys, copper microalloys, etc.), any other suitable conductive material, or any combination thereof. In some embodiments, the encapsulation layer 114 is formed of Al and is optionally pre-stressed, i.e., under tensile stress after being arranged on the core 112.
[0036] The encapsulation layer 114 may be arranged on the core 112 using any suitable process. In some embodiments, the encapsulation process 114 for arranging the encapsulation layer 114 around the core 112 uses a conformal machine. For example, the encapsulation process may be performed using a machine of similar functionality other than the conformal machine, and may optionally be further stretched to achieve target properties (e.g., a desired geometry or stress state) of the encapsulation layer 114. The conformal machine or similar machine used to arrange the encapsulation layer 114 may allow for quenching of the encapsulation layer 114. The conformal machine may be integrated with a pultrusion machine or stranding machine used to manufacture fiber reinforced composite strength members. Although Figure 1 A single encapsulation layer 114 is shown disposed about the core 112, but in some embodiments, multiple encapsulation layers 114 may be disposed about the core 112. In such embodiments, each of the multiple encapsulation layers 114 may be substantially similar to each other, or may be different from each other (e.g., formed of different materials, having different thicknesses, having different tensile strengths, etc.). In some embodiments, the core 112 may include a carbon fiber reinforced composite material, and the encapsulation layers 114 may include aluminum, such as pre-tensioned or pre-compressed aluminum.
[0037] In some embodiments, the interface between the core 112 and the encapsulation layer 114 may optionally include surface features, such as grooves, slots, cuts, indentations, detents, etc., to enhance adhesion, bonding, and / or interfacial locking between the radially outer surface of the core 112 and the radially inner surface of the encapsulation layer 114. Such surface features can facilitate the retention and preservation of stresses in the encapsulation layer 114 resulting from pre-tensioning. In some embodiments, the composite core 112 may have glass fiber tows arranged around its outer surface to form a spiral shape or twisted surface. In some embodiments, a braided or interwoven fiber layer is applied in the outer layer of the core 112 to promote interlocking or bonding between the core 112 and the encapsulation layer 114.
[0038] In some embodiments, the encapsulation layer 114 may have a thickness in the range of about 0.3 mm (inclusive) to about 5 mm (inclusive) or even higher (e.g., 0.3, 0.5, 1, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 mm (inclusive), or even higher). In some embodiments, the ratio of the outer diameter of the encapsulation layer 114 to the outer diameter of the core 112 is in the range of about 1.2:1 (inclusive) to about 5:1 (inclusive) (e.g., 1.2:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, or 5:1 (inclusive)).
[0039] In some embodiments, the strength member can have a minimum level of tensile strength, such as at least 600 MPa (e.g., at least 600, at least 700, at least 800, at least 1000, at least 1200, at least 1400, at least 1600, at least 1800, or at least 2000 MPa). In some embodiments, depending on the type of strength member and the degree of inflection point reduction, the elongation of the strength member 110 during pre-tensioning can include an elongation of at least 0.01% strain (e.g., at least 0.01%, at least 0.05%, at least 0.1%, at least 0.15%, at least 0.2%, at least 0.25%, at least 0.3%, at least 0.35%, at least 0.4%, at least 0.45%, or at least 0.5% strain (inclusive)), and the strength member 110 can be pre-tensioned before or after entering the conformable machine. In addition, the strength member 110 can be configured, for example, to have a composite core 112 with little to essentially no plastic deformation to withstand radial compression from crimping of conventional fittings, and radial pressure of at least 3 kN (e.g., at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, or at least 25 kN (inclusive)) during conforming during a draw-down process or folding forming.
[0040] In some embodiments, the encapsulation layer 114 may have an outer surface that is configured to be smooth and shiny (e.g., surface treated) so as to reduce absorptivity (i.e., enhance reflectivity) and thereby reduce the operating temperature of the core 112. Specifically, the smooth outer surface of the encapsulation layer 114 may be configured to reflect heat generated by the conductor layer 120 (e.g., the conductive strands forming the conductor layer 120) due to resistive heating of the conductor layer 120 due to the passage of current therethrough. The resistive heating may be particularly prominent on an outer layer forming the conductor layer or near an outer surface of the conductor layer 120 (e.g., near an outer surface of each conductive strand forming the conductor layer 120) due to the skin effect caused by the flow of electrons in an AC circuit near the outer surface.
[0041] By inhibiting heat transfer toward the core, the shiny encapsulation layer can prevent the temperature of the core 112 from exceeding its glass transition temperature or melting point. As described in further detail herein, the outer coating 130 can be formulated to have a high radiant emissivity in the wavelength range of 2.5 microns (inclusive) to 15 microns (inclusive) of thermal radiation. Although this may result in cooling of the conductor layer 120, the radiated heat will also propagate toward the strength member 110 and cause heating of the core 112, for example, causing the core 112 to be at a higher operating temperature than the conductor layer 120, which is undesirable. To reduce absorption of such emitted radiation, the outer surface of encapsulation layer 114 may be sufficiently reflective so as to provide a substantially reflective surface at an operating temperature of conductor 100 in the range of 90° C. to 250° C. (inclusive) (e.g., 90, 100, 120, 140, 160, 180, 200, 220, 240, or 250° C.) within the range of 2.5 microns to 15 microns (inclusive) (e.g., 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 6.0, 7.5, 8.0, 9.5, 10.5, 11.5, 12.5, 13.5, 14.5, 15.5, 16.5, 18.5, 19.5, 20.5, 21.5, 22.5, 23.5, 24.5, 25.5, 26.5, 27.5, 28.5, 29.5, 30.5, 31.5, 32.5, 33.5, 34.5, 35.5, 36.5, 37.5, 38.5, 39.5, 40.5, 41.5, 42.5, 43.5, 44.5, 45.5, 46.5, 47.5, 48.5, 49.5, 50.5 .5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 11, 12, 13, 14 or 15 microns (inclusive)) has an absorptivity of less than 0.6 (e.g., less than 0.55, less than 0.5, less than 0.45, less than 0.4, less than 0.35, less than 0.3, less than 0.25, less than 0.2, less than 0.15 or less than 0.1 (inclusive)) at a wavelength of 1.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 11, 12, 13, 14 or 15 microns (inclusive)).
[0042] In some embodiments, the outer surface of the encapsulation layer 114 is at least one of the following: treated, coated with a coating (e.g., inner coating 116), or otherwise configured so as to have a reflectivity greater than about 50% (e.g., greater than 50%, greater than 60%, greater than 65%, greater than 70%, greater than 75%, greater than 80%, greater than 85%, greater than 90%, or greater than 95% (inclusive)) at a thermal radiation wavelength corresponding to an operating temperature greater than about 90°C. In some embodiments, the outer surface has a reflectivity greater than about 55%. In some embodiments, the outer surface has a reflectivity greater than about 60%. In some embodiments, the outer surface has a reflectivity greater than about 65%. In some embodiments, the outer surface has a reflectivity greater than about 70%. In some embodiments, the outer surface has a reflectivity greater than about 75%. In some embodiments, the outer surface has a reflectivity greater than about 80%. In some embodiments, the outer surface has a reflectivity greater than about 85%. In some embodiments, the outer surface has a reflectivity greater than about 90%. In some embodiments, the outer surface has a reflectivity greater than about 95%.
[0043] In some embodiments, the outer surface of the encapsulation layer 114 can be surface treated (e.g., plasma treated, texturized, etc.) to have an absorptivity or reflectivity as described above. In some embodiments, the strength member 110 (i.e., the outer surface of the encapsulation layer 114) can be optionally coated with an inner coating 116 to reduce solar absorptivity. For example, the inner coating 116 can be disposed between the encapsulation layer 114 and the conductor layer 120. In some embodiments, the inner coating 116 can be formulated to have a thickness in the range of 2.5 microns (inclusive) to 15 microns (inclusive) (e.g., 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.0, 11.0, 12.0, 14.0, 16.0, 18.0, 19.0, 20.0, 21.0, 22.0, 23.0, 24.0, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0 The inner coating 116 may be configured to reflect a significant amount of radiation having a wavelength equal to or greater than 2.5 microns (e.g., heat radiated from the conductor layer 120 to the encapsulation layer 114) (e.g., at least 50% of the radiation having a wavelength equal to or greater than 2.5 microns incident on the encapsulation layer 114). In some embodiments, the thickness of the inner coating 116 may be in the range of 1 micron (inclusive) to 500 microns (inclusive) (e.g., 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, or 500 microns (inclusive)). In some embodiments, the inner coating 116 may have a reflectivity greater than about 50% (e.g., greater than 50%, greater than 60%, greater than 65%, greater than 70%, greater than 75%, greater than 80%, greater than 85%, greater than 90%, or greater than 95% (inclusive)) at a thermal radiation wavelength corresponding to an operating temperature greater than about 90° C. In some embodiments, the inner coating 116 may have a reflectivity greater than about 55%. In some embodiments, the inner coating 116 may have a reflectivity greater than about 60%. In some embodiments, the inner coating 116 may have a reflectivity greater than about 65%. In some embodiments, the inner coating 116 may have a reflectivity greater than about 70%. In some embodiments, the inner coating 116 may have a reflectivity greater than about 75%. In some embodiments, the inner coating 116 may have a reflectivity greater than about 80%. In some embodiments, the inner coating 116 may have a reflectivity greater than about 85%.In some embodiments, the inner coating 116 can have a reflectivity greater than about 90%. In some embodiments, the inner coating 116 can have a reflectivity greater than about 95%.
[0044] In some embodiments, the inner coating 116 may include nanopores, for example, voids or holes having a size equal to or less than 700 nm (e.g., in the range of 10 nm (inclusive) to 700 nm (inclusive)), so that the inner coating 116 has an absorptivity of less than 0.5, as described herein. The inner coating 116 may be formed of any suitable material and may include any suitable additives so that the inner coating 116 has an absorptivity of less than 0.5 microns, as described herein. In some embodiments, the inner coating 116 may include a binder and a reflector. In some embodiments, the inner coating 116 may also include a filler, a stabilizer, a colorant, a surfactant, and a reflector configured to enhance reflection within the range of 2.5 microns (inclusive) to 15 microns (inclusive). In some embodiments, the inner coating 116 may include an inorganic material and may be substantially free of organic material (e.g., having less than 10% organic material).
[0045] In some embodiments, the concentration of the binder in the inner coating 116 can be in the range of 20% (inclusive) to 60% (inclusive) (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%, including all ranges and values therebetween). In some embodiments, the concentration of the binder in the inner coating 116 can be at least 20%. In some embodiments, the concentration of the binder in the inner coating 116 can be up to 60%.
[0046] In some embodiments, the binder may include functional groups such as hydroxyl, epoxy, amine, acid, cyanate, silicate, silicate, ether, carbonate, maleic acid, etc. Inorganic binders may include, but are not limited to, metal silicates such as potassium silicate, sodium silicate, lithium silicate, and magnesium aluminum silicate, peptized monohydrated alumina, colloidal silica, colloidal alumina, aluminum phosphate, and combinations thereof In some embodiments, the inner coating 116 may include one or more reflective additives, including but not limited to cobalt, aluminum, bismuth, lanthanum, lithium, magnesium, neodymium, niobium, vanadium, iron, chromium, zinc, titanium, manganese, and nickel-based metal oxides and ceramics In some embodiments, the reflective additive may be used alone or in combination with a colorant in a concentration ranging from about 0.1% (inclusive) to about 5% (inclusive) (by the total weight of the dry ingredients of the inner coating).
[0047] In some embodiments, one or more stabilizers may be included in the inner coating 116, for example, at a concentration ranging from about 0.1% (inclusive) to about 2% (inclusive) (based on the total weight of the dry ingredients). Examples of stabilizers include, but are not limited to, dispersion stabilizers such as bentonite. One or more colorants may be used in the inner coating 116, for example, at a concentration ranging from about 0.02% (inclusive) to 0.2% (inclusive) (based on the total weight of the dry ingredients). The colorant can be an organic or inorganic pigment, including but not limited to titanium dioxide, rutile, titanium, anatase, brookite, cadmium yellow, cadmium red, cadmium green, orange cobalt, cobalt blue, cyan blue, golden yellow, cobalt yellow, copper pigment, azurite, Han purple, Han blue, Egyptian blue, malachite, Paris green, phthalocyanine blue BN, phthalocyanine green G, verdigris, chrome green, iron oxide pigment, blood red, mummy brown, red oxide, red ochre, Venetian red, Prussian blue, clay pigment, yellow ochre, raw ochre, burnt ochre, raw umber, burnt umber, marine pigment (ultramarine, ultramarine green), zinc pigment (zinc white, zinc ferrite) and combinations thereof. In some embodiments, one or more surfactants can also be used in the inner coating 116, for example, in a concentration of about 0.05% (inclusive) to about 0.5% (inclusive) (by the total weight of dry ingredients). Suitable surfactants include but are not limited to cationic, anionic or nonionic surfactants and fatty acid salts.
[0048] In some embodiments, the inner coating 116 may include Polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF), copolymers or any suitable combination thereof, these materials can be formulated as coatings and can include additives to increase solar reflectivity, i.e., reduce the absorptivity within the range of 2.5 microns (inclusive) to 15 microns (inclusive). In some embodiments, the inner coating 116 may include a polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) having a nanoporosity within the range of 50% or more, resulting in the inner coating 116 having an absorptivity of less than 0.5 at a wavelength within the range of 2.5 microns (inclusive) to 15 microns (inclusive) at an operating temperature within the range of 60°C (inclusive) to 250°C (inclusive), as described herein above. In some embodiments, the inner coating 116 may include nanocellulose fibers having a mesoporous structure. In some embodiments, the inner coating 116 may include alumina, SiO2, and porous PTFE.
[0049] In some embodiments, the inner coating 116 may include particles, for example, core-shell particles with a wide bandgap configured to reduce absorptivity. Such particles may include particles of inorganic materials such as Al2O3, BaSO4. Although TiO2 can be used, it may have a higher absorptivity, resulting in reduced effectiveness. In some embodiments, the inner coating 116 may include PVDF-HFP, which may be dissolved in a small amount of solvent (e.g., acetone) in, for example, a ball milling operation, and then dissolved in water, so that the inner coating 116 has a nanopore in the range of about 10nm (inclusive) to about 700nm (inclusive) (e.g., 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650 or 700nm (inclusive)). In some embodiments, such inner coating 116 may have a thickness within a range of 50 microns (inclusive) to 300 microns (inclusive) (e.g., 50, 100, 150, 200, 250, or 300 microns (inclusive)). In some embodiments, inner coating 116 may include one or more layers of silicon, ZnO, HfO2, TiO2, MgF2, Si3N4, Ta2O5, and / or ZnO2. In some embodiments, inner coating 116 may include silver.
[0050] In some embodiments, a primer, varnish, or adhesive of a coating may be applied to the outer surface of the encapsulation layer 114 to facilitate adhesion of the inner coating 116 to the encapsulation layer 114. The inner coating 116 may be applied in the form of a coating or slurry using any suitable method, such as brushing, dipping, spraying, evaporation, post-deposition curing or cross-linking, or shrink wrapping. In some embodiments, the outer surface of the encapsulation layer 114 may be cleaned, for example, by a solvent or using mechanical means (e.g., sandblasting), to facilitate adhesion of the inner coating 116 to the outer surface of the encapsulation layer 114. In some embodiments, the inner coating 116 may also be optionally disposed on the inner surface of the conductor layer 120 (e.g., the inner surface of a portion of the conductive strands included in the conductor layer 120 disposed proximate to the outer surface of the encapsulation layer 114). In some embodiments, the inner coating 116 may be substantially durable, tough, and / or scratch-resistant so as to protect the outer surface of the encapsulation layer 114 from damage, for example, during installation of the conductor layer 120 around the strength member 110.
[0051] As previously described, the strength member 110 may include a composite core 112 (e.g., including a carbon composite material) that may be black in color. Thus, the core 112 may act as a black body that absorbs radiation, resulting in the core 112 having a higher temperature relative to the conductor layer 120 or the encapsulation layer 114. This may further reduce the upper limit of the operating temperature of the conductor 100 by up to 10°C, thereby limiting the current carrying capacity of the conductor 100. Conversely, the encapsulation layer 110 having a highly reflective outer surface and / or the inner coating 116 having a low absorptivity reflects a significant portion of the heat emitted by the conductor layer 120 back into the environment. This may facilitate reducing the operating temperature of the core 112, thereby protecting the core 112, and enabling the conductor 100 to operate at a higher temperature relative to the core 112 so as to inhibit the temperature of the core 112 from exceeding a threshold temperature (e.g., its glass transition temperature or melting point).
[0052] In some embodiments, the inner coating 116 may include a multilayer coating deposited using any suitable deposition method such as physical vapor deposition (PVD), chemical vapor deposition (CVD), micro-arc oxidation (MAO), plasma arc oxidation (PAO), or any other suitable coating technology. In this way, a highly reflective coating is deposited on the encapsulation layer 114, which has high reflectivity at wavelengths of about 2 microns (inclusive) to about 15 microns (inclusive), and inhibits the encapsulation layer 114 from absorbing heat from the outer strands of the conductor layer 120. In some embodiments, the multilayer construction may include layers with different refractive indices and customized thicknesses to provide a nearly perfect reflective coating for the radiation wavelength in the temperature range of about 90° C. to about 250° C. In some embodiments, the same inner coating may be inserted between the encapsulation layer 114 and the core 112, for example, to achieve the same purpose of maintaining the core 112 at a lower operating temperature. In addition, the inner coating 116 may provide the encapsulation layer 114 with a low thermal conductivity to inhibit conductive heat transfer to the core 112.
[0053] The conductor layer 120 is arranged around the strength member 110 and is configured to transmit electrical signals therethrough at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive). In some embodiments, the conductor layer 120 may include a plurality of strands of conductive material arranged around the strength member 110. For example, the conductor layer 120 may include a first group of conductive strands arranged around the strength member 110 in a first winding direction (e.g., the strength member 110 is spirally wound in a first rotational direction), a second group of conductive strands arranged around the first group of strands in a second winding direction (e.g., the first group of conductive strands are spirally wound in a second rotational direction opposite to the first rotational direction), and may also include a third group of strands wound around the second group of strands in the first winding direction, and may further include any number of additional strands as desired.
[0054] In some embodiments, the conductor layer 120 (e.g., a plurality of strands of conductive material) may include, for example, aluminum, an aluminum alloy, copper, or a copper alloy including a microalloy as a conductive medium, etc. In some embodiments, the conductor layer 120 may include a conductive strand including a Z, C, or S wire to hold the outer strand in place. The conductor layer 120 may have any suitable cross-sectional shape, such as a circle, a triangle, a trapezoid, etc. In some embodiments, the conductor layer 120 may include a stranded aluminum layer that may be circular or trapezoidal. In some embodiments, the conductor layer 120 may include a Z-shaped aluminum strand. In some embodiments, the conductor layer 120 may include an S-shaped aluminum strand. In some embodiments, the conductor 100 may include any conductor layer described in U.S. Patent No. 9,633,766, filed on September 23, 2015, entitled “Energy Efficient Conductors with Reduced Thermal Knee Points and the Method of Manufacture Thereof”, the entire disclosure of which is incorporated herein by reference.
[0055] In some embodiments, the strength member 110 may be optionally tensioned while a conductor layer 120 of aluminum or copper or their respective alloys arranged around the strength member 110 may be applied to form the conductor 100 into a sticky conductive hybrid rod that can be wound on a conductor spool. In some embodiments, to facilitate winding of the conductor onto the spool and to facilitate easy springback of the conductor, the conductor 100 may be optionally configured as a non-circular (e.g., oval) shape so that the minor axis (of the conductor 100) is subjected to bending around the spool (or sheave during conductor installation) to facilitate a smaller bend or spool radius, while the strength member 110 may be configured with a major axis to facilitate springback during installation. The entire conductor 100 may be circular, with a non-circular strength member 110 or multiple strength members 110 arranged in a non-circular shape, and the winding bend direction may be along the major axis of the strength member 110 to facilitate springback without excessively subjecting the conductor layer 120 to additional compressive forces due to the winding bend.
[0056] To further facilitate winding the conductor layer 120 onto the strength member 110, in some embodiments, the conductor layer 120 can include multiple sections, such as strands or multiple groups of strands or wires (e.g., 2, 3, 4, etc.) of conductive material, and each section is bonded to the strength member 110 while maintaining compressive stress, and the sections are rotated one or more full turns (equal to one complete winding in a spool) along the length of the conductor 100 to facilitate easy winding. Thus, the conductor 100 can be configured to have a negligible skin effect (i.e., the conductive layer thickness is less than the required skin depth at AC circuit frequencies), while the strength member 110 can be under sufficient residual tensile stress, and the conductor layer 120 (e.g., each strand of conductive material) is mostly free of tension or under compressive stress. In some embodiments, the strands of conductive material can be formed by a conformable machine, for example, by extruding a heat-deformable (e.g., semi-solid) conductive material (e.g., aluminum) from a mold. The strands can be molded into a circular, trapezoidal, or any other desired shape. In some embodiments, the extrusion die or die may have a strand twist coefficient defined therein such that during the stranding operation of the conductive strands, shaping (e.g., removing sharp corners or edges of the conductive strands to avoid corona, as is done in conventional stranding operations) may not be required. In some embodiments, the conductive medium may be extruded from the die or die at an angle to form the conductive strands wrapped around the strength member 110 at an angle, as described herein.
[0057] In some embodiments, for AC applications where the skin effect is prominent, the conductor layer 120 may include multiple layers of conductive strands arranged concentrically around the strength member 110, wherein each layer has a limited thickness to maximize the skin effect at a minimum conductor content, thereby achieving the lowest AC resistance. In some embodiments, the conductor layer 120 may be optionally twisted to facilitate winding the conductor around a reasonably sized reel and to facilitate conductor stringing. In some embodiments, if more aluminum or copper is used, the outermost strands contained in the conductor layer 120 may be TW, C, Z, S, or round strands, as this does not cause permanent local distortion problems (i.e., the inner strands of the conductor layer 120 may not deform so that they prevent the outer strands from properly relocating after tension is released or reduced). Thus, the smooth outer surface and compact construction can effectively reduce wind loads and ice accumulation on the conductor 100, thereby reducing sag caused by ice or wind-related weather events.
[0058] In some embodiments, the conductor 100 may be prestressed, for example, by subjecting the conformable conductor 100 to a paired tensioner method or trimming a predetermined core 112 length prior to dead-ending, all without applying high tensile stress to the crossarms to pre-tension conventional conductors in utility poles. For example, during stringing operations, the conductor 100 may be pre-tensioned using multiple sets of large gears prior to the first sheave without applying additional loads to the tower. For example, this may be accomplished with two sets of tensioners, the first set maintaining normal back tension on the conductor drum / spool, while the second set restores normal stringing tension to avoid excessive loading on the pole or tower (e.g., an old tower in a reconstruction project). The conductor 100 may be subjected to a pre-tensioning stress between the first and second tensioners, for example, about 2x the average conductor daily tensile load, to ensure that the pre-tensioning drives its inflection point below normal operating temperature, keeps the conductor layer 120 out of tension for optimal self-damping, and the conductor 100 does not substantially change its sag with temperature. In some embodiments, conductor layer 120 (e.g., each strand of conductive material included in conductor layer 120) may include aluminum having an electrical conductivity of at least 50% ICAS, at least 55% ICAS, at least 60% ICAS, or at least 65% ICAS, or may include copper having an electrical conductivity of at least 65% ICAS, at least 75% ICAS, or even at least 95% ICAS.
[0059] The conductor 100 may combine pre-tensioning with a strength member 110, which may include an encapsulation layer 114 formed of a conductive material having sufficient compressive strength and thickness to substantially maintain the pre-tensioning stress in the strength member 110 while leaving the conductor layer 120 disposed around the strength member 110 substantially free of tension or in compression after the conductor is installed in the field, and maintaining the low thermal expansion characteristics of the strength member 100. The conductor 100 may have an inherently lower thermal inflection point. Unlike gap-type conductors where the conductor, accessories, installation, and repair are very expensive requiring complex installation tools and processes, the conductor 100 may be easy to install and repair while maintaining low sag, high capacity, and energy efficiency due to the shift in inflection point.
[0060] In some embodiments, a metallurgical bond may be provided between the strength member 110 and the conductor layer 120. In some embodiments, an adhesive (e.g., Chemlok 250 from Lord Corporation) may be applied to the surface of the strength member 110 of the conductor 100 to further promote adhesion between the strength member 110 and the conductor layer 120 disposed thereon. Additionally, surface features on the strength member 110 may be incorporated to promote adhesion between the conductor layer 120 and the strength member 110 (e.g., a stranded strength member 110, such as a C-bonded conductor used in conventional conductors). 7or steel wire; pultruded composite cores with protruding or depleted surface features; and intentionally roughened surfaces on strength members, such as CTC Global's ACCC cores, where single or multiple strands of glass or basalt or similar other types of insulating materials are arranged around strength member 110, rather than just longitudinally parallel configurations (described in the patent). In some embodiments, conductor layer 120 may include aluminum, aluminum alloys, copper and copper alloys, lead, tin, indium tin oxide, silver, gold, non-metallic materials with conductive particles, any other conductive material, conductive alloy or conductive composite material, or a combination thereof.
[0061] It should be understood that the conductor layer 120 can be in a state without substantial tension, while the strength member 110 can be pre-stretched / tensioned. After the pre-tension in the strength member 110 is released, the conductor layer 120 can be compressed, which can minimize the retraction of the strength member 110. The strength member 110 made of composite material can have a strength greater than 80 ksi, a modulus from 5 msi to 40 msi, and a strength of about 1x10 -6 / ℃(inclusive)~about 8x10 -6 / ℃ (inclusive) CTE.
[0062] The level of pre-tensioning in the conductor 100 may depend on the conductor size, conductor construction, conductor application environment, and desired target thermal inflection point. If the goal is to have the conductor thermal inflection point at or near the stringing temperature (e.g., ambient temperature), the desired tension on the strength member 110 may only be about the same stringing sag tension (e.g., about 10% (inclusive) to about 20% (inclusive) of the rated conductor strength), plus an additional stringing sag tension level of about 5% (inclusive) to about 50% (inclusive) (e.g., about 10% (inclusive) to about 30% (inclusive)) to keep all the aluminum (or copper, in the case of copper conductors) contained in the conductor layer 120 tension-free after stringing, which is much lower than the conductor pre-tensioning in the tower where a load of about 40% of the conductor tensile strength is typically used. If a lower thermal inflection point is desired, a higher pre-tensioning stress may be used. It is also important to note that the composite core 112 of the strength member 110 can include strong, lightweight carbon fibers with low thermal sag. The use of fiber reinforced composite encapsulated strength members 110 is particularly advantageous where the resilient strength members 110 facilitate springing back of the encapsulated strength members 110 from a rolled configuration for field installation. In some embodiments, the strength members 110 can be pre-strained by at least 0.05% (e.g., at least 0.05%, at least 0.1%, at least 0.15%, at least 0.2%, at least 0.25, or at least 0.3%, inclusive).
[0063] In some embodiments, for example, for AC power transmission applications, the conductor layer 120 may include concentric multiple layers (e.g., multiple strands) of conductive media arranged around the strength member 110 during the conformal process. The skin depth may be adjusted based on the power transmission frequency. In some embodiments, for pure copper, the skin depth may be in the range of about 6 mm (inclusive) to about 12 mm (inclusive) at 60 Hz (e.g., 6, 7, 8, 9, 10, 11, or 12 mm (inclusive)), or in the range of about 12 mm (inclusive) to about 20 mm (inclusive) at 25 Hz (e.g., 12, 13, 14, or 15 mm (inclusive)). For pure aluminum, the skin depth can be in the range of about 9 mm (inclusive) to about 14 mm (inclusive) at 25 Hz (e.g., 9, 10, 11, 12, 13, or 14 mm (inclusive)), and in the range of about 14 mm (inclusive) to about 20 mm (inclusive) at 60 Hz (e.g., 14, 15, 16, 17, 18, 19, or 20 mm (inclusive)). The thickness of each strand of conductive medium included in the conductor layer 120 can be less than the maximum allowed depth, for example, to achieve low A / C resistance. In some embodiments, each conductive strand included in the conductor layer 120 can include copper having a thickness of up to 12 mm (e.g., up to 12, up to 11, up to 10, up to 9, or up to 8 mm (inclusive)). In some embodiments, each conductive strand included in the conductor layer 120 can include aluminum having a thickness of up to 16 mm (e.g., up to 16, up to 14, up to 13, up to 12, up to 11, or up to 10 mm (inclusive)). In some embodiments, a dielectric coating may be inserted between the conductive strands to optimize the skin effect. In some embodiments, a lubricant may be provided between adjacent conductive strands to facilitate some relative movement of the conductive strands contained in the conductor layer 120.
[0064] In some embodiments, the interface between the strength member 110 and the conductor layer 120 can be further optimized with surface features in the strength member 110 that enhance the interfacial locking and / or bonding between the strength member 110 and the conductor layer 120 to maintain and preserve the stresses resulting from the pre-tensioning. Such features can include, but are not limited to, protruding features on the outer surface of the strength member 110 (e.g., the outer surface of the encapsulation layer 114 of the inner coating 116) and the rotation of the strength member 110 around the axial direction. In addition, the same features can be incorporated into the interface between the subsequent conductive strands contained in the conductor layer 120. In some embodiments, the strength member 110 can include a glass fiber strand arranged around its surface to form a spiral shape or a twisted surface. In some embodiments, a braided or interwoven fiber layer is applied in the outer layer of the strength member 110 to promote interlocking or bonding between the strength member 110 and the conductor layer 120. The steel wire can be shaped to have similar surface features. In some embodiments, the strength member 110 can be pre-tensioned by pre-tensioning the reinforcing fibers in a matrix of a conductive medium such as aluminum or copper or their respective alloys. Such reinforcing fibers may include ceramic fibers, non-metallic fibers, carbon fibers, glass fibers, and / or other similar types of fibers.
[0065] In some embodiments, an insulating layer 122 (e.g., a jacket) may be optionally disposed around the conductor layer 120. The insulating layer 122 may be formed of any suitable electrically insulating material, such as rubber, plastic, or polymer (e.g., polyethylene, PTFE, high-density polyethylene, cross-linked high-density polyethylene, etc.). The insulating layer 122 may be configured to electrically isolate or shield the conductor 100. In some embodiments, the insulating layer 122 may not be included.
[0066] In some embodiments, the outer surface of the conductor layer 120 (e.g., the outer surface of the outermost conductive strand or the outer surface of each conductive strand) or the insulating layer is treated with features and / or includes features so that the outer surface has a solar absorptivity of less than 0.6 (e.g., less than 0.55, less than 0.5, less than 0.45, less than 0.4, less than 0.35, less than 0.3, less than 0.25, less than 0.2, less than 0.15, or less than 0.1 (inclusive)). In some embodiments, the outer surface has a solar absorptivity of less than 0.55. In some embodiments, the outer surface has a solar absorptivity of less than 0.5. In some embodiments, the outer surface has a solar absorptivity of less than 0.45. In some embodiments, the outer surface has a solar absorptivity of less than 0.4. In some embodiments, the outer surface has a solar absorptivity of less than 0.35. In some embodiments, the outer surface has a solar absorptivity of less than 0.30. In some embodiments, the outer surface has a solar absorptivity of less than 0.25. In some embodiments, the outer surface has a solar absorptivity of less than 0.20. In some embodiments, the outer surface has a solar absorptivity less than 0.15. In some embodiments, the outer surface has a solar absorptivity less than 0.10.
[0067] As described herein, some conductors typically include a conductor layer having conductive strands that have a shiny outer surface. Such a shiny outer surface may pose a driving hazard because it reflects sunlight into the eyes of individuals who may be traveling on a road near the conductor. In contrast, the outer surface of the conductor layer 120 (e.g., the outer surface of one or more conductive strands included in the conductor layer 120 or at least a portion of the outer surface) may be treated or otherwise configured to have a low reflectivity to mitigate reflection hazards. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 50% corresponding to an operating temperature greater than 90°C. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 45%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 40%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 35%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 30%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 25%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 20%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 15%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of less than 10%.
[0068] In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 10%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 15%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 20%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 25%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 30%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 35%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 40%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 45%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of no more than 50%.
[0069] In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity in the range of 5% (inclusive) to 50% (inclusive). In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity in the range of 10% (inclusive) to 45% (inclusive). In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity in the range of 15% (inclusive) to 40% (inclusive). In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity in the range of 20% (inclusive) to 30% (inclusive). Combinations of the above reflectivities are also possible (e.g., at least about 5% and not more than about 50%, or at least about 10% and not more than about 40%), including end values. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 50%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 45%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 40%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 35%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 30%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 25%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 20%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 15%. In some embodiments, the outer surface of the conductor layer 120 may be treated or otherwise configured to have a reflectivity of about 10%.
[0070] Any suitable treatment or process may be used to configure the outer surface of the conductor layer 120 to have low reflectivity. In some embodiments, the outer surface of the conductor layer 120 or at least a portion of the outer surface of the conductor layer 120 (e.g., the outer surface of the outermost conductive strands forming the conductor layer 120) may be sandblasted to reduce its reflectivity.
[0071] In some embodiments, the outer surface of the conductor layer 120 or at least a portion thereof may be brushed to produce grooves, dents, defects, matte finishes on the outer surface of the conductor layer 120 to reduce the reflectivity of the outer surface. For example, the brush may include a rotating brush having a plurality of metal bristles (e.g., steel bristles) or other bristles formed of a hard material (e.g., carbon or diamond). As the brush rotates, the conductor 100 may be translated close to the bristles of the brush, or alternatively, the brush may be translated along the axial length of the conductor 100 so that the bristles of the rotating brush contact the outer surface of the conductor layer 120 and produce grooves, dents, or other defects on the outer surface of the conductor layer 120. In some embodiments, two or more rotating brushes may be used. For example, the conductor 100 may be translated between two brushes rotating in the same or opposite directions so that the bristles of the opposing brushes contact the outer surface of the conductor layer 120 and produce grooves or defects. Relative to reducing reflectivity by sandblasting, reducing defects by brushing may produce minimal debris, so that any substantial cleaning of the conductor 100 after brushing may not be required.
[0072] As described herein, the current carrying capacity of the conductor layer 120, and therefore the current carrying capacity of the conductor 100, is limited by the operating temperature of the conductor 100. It is desirable to maintain the operating temperature of the conductor 100 below a threshold temperature (e.g., the glass transition temperature or melting point of the core 112), for example, to prevent damage to the core 112. To reduce the operating temperature of the conductor 100, the conductor 100 may further include an outer coating 130 disposed on the conductor layer 120. As described herein, the outer coating 130 may be disposed on the outer surface of the conductor layer 120 in addition to, or in the alternative to, the outer surface of the conductor layer 120 being treated or otherwise configured to reduce its reflectivity. The outer coating 130 is formulated to have a solar absorptivity of less than 0.6 (e.g., less than 0.6, less than 0.55, less than 0.5, less than 0.45, less than 0.40, less than 0.35, less than 0.30, less than 0.25, less than 0.20, less than 0.15, less than 0.1 (inclusive), or even lower) at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and a radiant emissivity greater than 0.5 (e.g., greater than 0.50, greater than 0.55, greater than 0.60, greater than 0.65, greater than 0.70, greater than 0.75, greater than 0.80, greater than 0.85, greater than 0.90, greater than 0.95 (inclusive), or even higher) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive).
[0073] In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.55. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.50. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.45. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.40. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.35. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.30. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.25. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.20. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.15. In some embodiments, the outer coating 130 is formulated to have a solar absorptivity of less than 0.10. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.55. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.60. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.65. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.70. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.75. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.80. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.85. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.90. In some embodiments, the outer coating 130 is formulated to have a radiant emissivity greater than 0.95. For example, coating 130 can be formulated to have a radiant emissivity equal to or greater than 0.75 (e.g., 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95 (inclusive), or even higher) at an operating temperature of about 200° C. at a wavelength of about 6 microns and a solar absorptivity less than 0.3 (e.g., 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.15, 0.10 (inclusive), or even lower) at a wavelength of less than 2.5 microns.
[0074] The low solar absorptivity of the outer coating 130 at wavelengths less than 2.5 microns causes the outer coating 130 to reflect a large amount of solar radiation at wavelengths less than 2.5 microns (e.g., greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or even greater than 95% of the incident solar radiation), thereby reducing solar absorption and suppressing the increase in the operating temperature of the conductor 100. In addition, the high radiation emissivity of the outer coating 130 at wavelengths in the range of 2.5 microns to 15 microns causes the outer coating 130 to emit the heat generated by the conductor 100 due to the passage of current therein in the form of photons. This increases the radiation of heat from the conductor 100 to the environment, further reducing the operating temperature of the conductor 100. In some embodiments, the outer coating 130 can cause a reduction in the operating temperature of the conductor 100 at a particular current within a range of about 5° C. (inclusive) to about 40° C. (inclusive) (e.g., 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 25, 30, 35, or 40° C. (inclusive)). As a result, the conductor 100 can operate at a lower temperature at the same current carrying capacity. Conversely, the current carrying capacity of the conductor 100 can be increased at the same operating temperature relative to a conductor that does not include the outer coating 130. In some embodiments, where a coupler mechanism is, for example, crimped to an axial end of the conductor 100 to couple the conductor 100 to another conductor, or a closed-end fitting for coupling the conductor 100 to a transmission pole or tower, the outer coating 130 can also be applied to such fittings, couplers, or tensioning hardware, such as closed-end couplers, spliced couplers, suspension clamps, or any other suitable fittings or couplers to keep the temperature of such fittings as low as possible and extend their life.
[0075] In some embodiments, the unique properties of the outer coating 130 can be caused by including microstructures and nanopores in the outer coating 130. For example, the outer coating 130 can include a microstructure having a size in the range of 3 microns (inclusive) to 15 microns (inclusive) (e.g., 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 microns (inclusive)), which is configured to make the outer coating 130 have a radiant emissivity greater than 0.5, as described above. In some embodiments, the microstructure can include micropores or voids, which can be inherently present in the outer coating 130, or introduced during the manufacturing operation (e.g., ball milling operation) of the outer coating 130.
[0076] In some embodiments, the microstructure may include inorganic particles. For example, the microstructure may include metal oxides, metal nitrides, metal fluorides, metal carbides, metal carbonates and / or rare earth elements. In some embodiments, the microstructure includes CaCO3 or other carbonate compounds, such as BaCO3, MgCO3, Li2CO3, Na2CO3, K2CO3 or any similar compounds, such as solid particles, hollow particles and / or core-shell particles. The carboxyl bond of CaCO3 has an absorption wavelength of about 6 microns, which enhances the radiation emissivity, thereby enhancing radiation cooling, especially at an operating temperature of about 200°C. Ionic carbonates have strong absorption at 7 microns, while covalent carbonate bonds have strong absorption at 5.5 microns to 6 microns, and have many other strong absorption peaks from 7 microns (inclusive) to 13 microns (inclusive). In some embodiments, other compounds with wavelength absorption activity in the range of 3 to 15 microns may also be considered as carbonate substitutes or in combination with carbonates.
[0077] In some embodiments, the microstructures may include silica (e.g., porous silica or randomly distributed SiO2 spheres in a polymer matrix). In some embodiments, the microstructures may include Al2O3 (e.g., porous alumina) particles, BaSO4 particles, or wide bandgap pigments. In some embodiments, the microstructures may include core-shell particles and / or wide bandgap and multi-scale particles that promote reflection of incident sunlight while having vibrational modes that provide radiant emissivity in the range of 2.5 microns to 15 microns. In some embodiments, the core-shell particles may be implemented by sol-gel coatings or hollow particles such as hollow silica, hollow microbeads, etc. In some embodiments, the microstructure may include gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide, manganese oxide, chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, tricalcium phosphate, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, magnesium oxide, calcium oxide, any other suitable material, or combinations thereof.
[0078] The outer coating 130 also includes nanopores having a size in the range of about 30 nm (inclusive) to about 700 nm (inclusive) (e.g., 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 25, 300, 350, 400, 450, 500, 550, 600, 650, or 700 nm (inclusive)), which are configured to allow the outer coating 130 to have a solar absorptivity in the range of less than 0.5. For example, the outer coating 130 may include voids or holes having a size in the range of about 50 nm (inclusive) to about 500 nm (inclusive).
[0079] In some embodiments, the outer coating 130 may include fluoropolymers and / or polyurethanes. In some embodiments, the fluoropolymers may include PVDF-HFP polymers and / or PVDF-HFP copolymers. The ethylene functional groups in HFP have CC bonds and CH bonds, and CC bonds and CH bonds have several vibration modes corresponding to about 3.5 microns, about 6.9 microns, and about 13.8 microns. Polyvinylidene fluoride has CC bonds, CH bonds, and CF bonds with multiple vibration modes at wavelengths greater than about 7 microns, and is therefore a strong broadband emitter. Therefore, PVDF-HFP can exhibit high radiative emissivity (e.g., equal to or greater than 0.9) in the range of 2.5 microns to 15 microns.
[0080] In some embodiments, to form the PVDF-HFP outer coating 130, the PVDF-HFS can be dissolved in a small amount of acetone (VOC), and then the solution is diluted with water. A bimodal porosity distribution (e.g., nanopores of about 200 nm for reducing solar absorptivity, and micropores in the range of about 5 microns (inclusive) to about 10 microns (inclusive) for high radiation emissivity) can be achieved by ball milling. In some embodiments, the microstructure can be included in the coating composition (e.g., in the form of a slurry or colloid). In some embodiments, the outer coating 130 may have a thickness in the range of about 50 microns (inclusive) to about 500 microns (inclusive) (e.g., 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, 420, 440, 460, 480, or 500 microns (inclusive)). In some embodiments, before the outer coating 130 is disposed on the outer surface of the conductor layer 120, a primer, varnish, or adhesive may be applied to the outer surface of the conductor layer 120 (e.g., on each conductive strand forming the conductor layer 120, only on the outermost conductive strand forming the conductor layer 120, or on the outer surface of the insulating layer 122 that may be disposed around the conductor layer 120).
[0081] In some embodiments, the outer surface of at least a portion of the conductive strands forming the conductor layer 120 can be cleaned, for example, using a surfactant or solvent, to provide a clean surface for depositing the outer coating 130. In some embodiments, the outer surface of the conductor layer 120 (e.g., the outer surface of each strand, the outermost strand, or the outermost strand forming the conductor layer 120) or the insulating layer 122 can be roughened (e.g., by sandblasting, brushing, etc.) to provide a rough surface to facilitate adhesion of the outer coating 130 thereto. This benefit can be provided in addition to the reduction in specular reflection and reflectivity of the outer surface that can be achieved by such treatment. In some embodiments, the primer and / or the outer coating 130 can be hydrophobic, for example, to inhibit icing, inhibit scaling, prevent ultraviolet radiation, and inhibit water-borne fouling.
[0082] In some embodiments, the outer coating 130 may include PTFE or any other dielectric. In some embodiments, the outer coating 130 may include nanocellulose fibers. In some embodiments, the microstructure may include TiO2 with high emissivity to provide high radiative emissivity of the outer coating 130, and the nanopores contained in the outer coating 130 may provide low solar absorptivity. In some embodiments, the outer coating 130 may also include a color or dye (e.g., a fluorescent dye) to provide limited near infrared and short wave infrared absorption.
[0083] In some embodiments, the outer coating 130 may include a coating having a resin matrix, such as a black coating, such as a polyurethane coating, and may optionally include ceramic particles. In some embodiments, the outer coating 130 may include a suitable fluorine-containing copolymer compound of about 50% (inclusive) to about 99% (inclusive) by dry weight (for example, about 75% (inclusive) to about 95% (inclusive) by dry weight). In some embodiments, the outer coating 130 may include a polymer cross-linked by any suitable method, which includes, for example, moisture curing, chemical curing, thermal curing, UV curing, infrared (IR) curing and / or electron beam curing methods. The cross-linking agent may include, but is not limited to, a cross-linking agent reactive to hydroxyl, acid, epoxide, amine, cyanate ester of a monomer or oligomer or polymer in liquid, semi-solid or powder form, which monomers or oligomers or polymers have urethane, fluorine, silane, fluorosilane, fluorosilicone, silsesquioxane, polytetrafluoroethylene ("PTFE"), epoxy, phenol, ether, silicone or acrylic groups in the main chain or grafted alone or in combination with other functional groups. Suitable chemical crosslinking agents (e.g., reactants) may include monomers or oligomeric polymer resins that can promote the curing of the composition when mixed with a crosslinkable fluorinated copolymer. In some embodiments, the crosslinking agent may include acrylates, fluorosilanes, fluorosilicones, methacrylates, silanes (including methoxysilanes and epoxysilanes) metal catalysts, triallyl isocyanurate ("TAIC"), peroxides, or combinations thereof. In some embodiments, the fluorinated copolymer may, for example, have hydroxyl groups that can be crosslinked with a polyisocyanate crosslinker such as hexamethylene-6,6-diisocyanate ("HDI"). Such HDI crosslinkers may be aromatic or aliphatic. In some embodiments, a catalyst may be additionally included to accelerate the crosslinking reaction. A suitable crosslinking agent may be included in an amount of about 1% (inclusive) to about 20% (inclusive) of the outer coating 130 by dry weight.
[0084] In some embodiments, the outer coating 130 may include additional components, such as one or more fillers (e.g., microstructures), solvents, defoamers, emulsifiers, thickeners, UV and light stabilizers, or resins. In some embodiments, the outer coating 130 may include metal oxides, metal nitrides, metal fluorides, rare earth elements, and metal carbides, such as but not limited to gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide ("silica"), chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, HfO2, BaSO4, and combinations thereof. Certain fillers, such as boron oxide, zinc oxide, cerium oxide, silicon dioxide, and titanium dioxide, may act as emissives to improve the radiation of heat from the outer coating 130.
[0085] In some embodiments, suitable rare earth materials may include one or more of rare earth oxides, rare earth carbides, rare earth nitrides, rare earth fluorides, or rare earth borides. Examples of rare earth oxides include scandium oxide, yttrium oxide, lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, thulium oxide, ytterbium oxide, and lutetium oxide. Examples of rare earth carbides include, but are not limited to, scandium carbide, yttrium carbide, cerium carbide, praseodymium carbide, neodymium carbide, samarium carbide, europium carbide, gadolinium carbide, terbium carbide, dysprosium carbide, holmium carbide, erbium carbide, thulium carbide, ytterbium carbide, and lutetium carbide. Examples of rare earth fluorides include, but are not limited to, scandium fluoride, yttrium fluoride, cerium fluoride, praseodymium fluoride, neodymium fluoride, samarium fluoride, europium fluoride, gadolinium fluoride, terbium fluoride, dysprosium fluoride, holmium fluoride, erbium fluoride, thulium fluoride, ytterbium fluoride, and lutetium fluoride. Examples of rare earth borides include, but are not limited to, scandium boride, yttrium boride, lanthanum boride, cerium boride, praseodymium boride, neodymium boride, samarium boride, europium boride, gadolinium boride, terbium boride, dysprosium boride, holmium boride, erbium boride, thulium boride, ytterbium boride, and lutetium boride.
[0086] In some embodiments, the filler may also include a conductive filler, including carbon nanotubes, graphene, and graphite. A sufficient amount of such conductive fillers may make the outer coating 130 coating conductive or semi-conductive. In addition, such fillers may improve the heat transfer performance of the outer coating 130. In some embodiments, the filler may have an average particle size of about 50 microns or less (e.g., about 10 microns or less, or about 500 nanometers or less). The outer coating 130 may optionally include a suitable filler of less than about 50% by weight (e.g., about 1% (inclusive) to about 50% (inclusive) by weight, or about 5% (inclusive) to about 20% (inclusive) by weight).
[0087] In some embodiments, the outer coating 130 may include, for example, a defoamer to inhibit or delay the formation of foam (e.g., when water is added to the heat-resistant coating composition). Suitable examples of defoamers may include silicon-based defoamers and non-silicon-based defoamers. In some embodiments, surfactants may also be used as defoamers. Suitable surfactants may include, but are not limited to, cationic, anionic or nonionic surfactants and fatty acid salts. In some embodiments, the defoamer may be about 0.1% (inclusive) to about 5% (inclusive) of the outer coating 130 by weight.
[0088] In some embodiments, the outer coating 130 may include, for example, an emulsifier to maintain a uniform dispersion of the compound in the aqueous solution. Suitable emulsifiers may include, but are not limited to, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, potassium stearate, sodium dioctyl sulfosuccinate, dodecane diphenoxy disulfonate, nonylphenoxyethyl poly (1) ethoxyethyl ammonium sulfate, sodium styrene sulfonate, sodium dodecyl allyl succinate sulfonate, linseed oil fatty acid, sodium or ammonium salt of ethoxylated nonylphenol phosphate, sodium octoxynol-3-sulfonate, sodium coconut creatine, sodium 1-alkoxy-2-hydroxypropyl sulfonate, α-olefin (C 14 -C 16 ) sodium sulfonate, hydroxyalkanol sulfate, N-(1,2-dicarboxyethyl)-N-octadecylsulfosalicylic acid amine tetrasodium salt, N-octadecylsulfosalicylamino acid disodium salt, alkylamidopolyethoxysulfosuccinate disodium, ethoxylated nonylphenolsulfosuccinate half ester disodium, ethoxyethyl sodium sulfate. The outer coating 130 may contain an emulsifier in an amount ranging from about 2% (inclusive) to about 3% (inclusive) by weight of the outer coating 130.
[0089] In certain embodiments, a coalescing agent or thickener may be added to improve the formation of a thin film on the outer coating 130. In such embodiments, a coalescing agent may be included that is about 20% or less by weight of the coating composition (e.g., in the range of about 2% (inclusive) to about 10% (inclusive) by weight). In certain embodiments, a UV or light stabilizer may be added to the outer coating 130 to improve external weather resistance. Suitable UV or light stabilizers may include benzotriazole-type, triazine-type UV absorbers and HALS compounds. In the outer coating 130, about 0.1% (inclusive) to about 5% (inclusive) by weight of UV or light stabilizers may be included. Additional resins may be included in the outer coating 130 to improve the performance of the outer coating 130. For example, one or more acrylic, silicone, polyurethane, silane, fluorosilane, silsesquioxane or epoxy resins may be added to the outer coating 130. Alternatively or additionally, commercial lubricants, waxes and friction reducers may be added to the coating composition. Such resins can improve various properties of the composition, including, for example, processability, durability, and service life of the coating. In the outer coating 130, about 0.1% to about 40% by weight, inclusive, of a suitable resin can be included.
[0090] In some embodiments, the outer coating 130 may contain one or more binders, for example, in the range of about 10% to about 70% (for example, about 10% to 20%, about 20% to 30%, about 30% to 40%, about 40% to 50%, about 50% to 60%, or about 60% to 70%) based on the total weight of the dry ingredients of the outer coating 130. The binder may include functional groups such as hydroxyl, epoxy, amine, acid, cyanate, silicate, silicate, ether, carbonate, maleic acid, methyltrimethoxysilane, etc. The inorganic binder may be, but is not limited to, metal silicates such as potassium silicate, sodium silicate, lithium silicate, and magnesium aluminum silicate; peptized monohydrated alumina; colloidal silica; colloidal alumina, aluminum phosphate, and combinations thereof.
[0091] One or more heat radiating agents may be included in the outer coating 130, for example, at a concentration of about 1% (inclusive) to about 20% (inclusive) (based on the total weight of the dry components of the outer coating 130). The heat radiating agent includes, but is not limited to, gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide, manganese oxide, chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, tricalcium phosphate, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, magnesium oxide and calcium oxide, and combinations thereof.
[0092] In some embodiments, one or more reflective additives may also be included in the outer coating 130. Such reflective additives may include, but are not limited to, cobalt, aluminum, bismuth, lanthanum, lithium, magnesium, neodymium, niobium, vanadium, iron, chromium, zinc, titanium, manganese and nickel-based metal oxides and ceramics. The reflective additive may be included in a concentration of about 0.1% (inclusive) to about 5% (inclusive) (by the total weight of the dry ingredients) alone or mixed with a colorant. In some embodiments, one or more stabilizers may be used in the coating composition, for example, at a concentration of about 0.1% (inclusive) to about 2% (inclusive) (by the total weight of the dry ingredients). Examples of stabilizers include, but are not limited to, dispersion stabilizers, such as bentonite.
[0093] In some embodiments, one or more colorants may be used in the coating composition of the outer coating 130, for example, at a concentration of about 0.02% (inclusive) to 0.2% (inclusive) (based on the total weight of dry ingredients). The colorant may be an organic or inorganic pigment, including but not limited to titanium dioxide, rutile, titanium, anatase, brookite, cadmium yellow, cadmium red, cadmium green, orange cobalt, cobalt blue, cyan blue, golden yellow, cobalt yellow, copper pigment, azurite, Han purple, Han blue, Egyptian blue, malachite, Paris green, phthalocyanine blue BN, phthalocyanine green G, verdigris, chrome green, iron oxide pigment, blood red, mummy brown, red oxide, red ochre, Venetian red, Prussian blue, clay pigment, yellow ochre, raw ochre, burnt ochre, raw umber, burnt umber, marine pigment (ultramarine, ultramarine green), zinc pigment (zinc white, zinc ferrite) and combinations thereof. In some embodiments, the outer coating 130 may contain organic materials (e.g., less than about 5% of organic materials). For example, the coating composition may include sodium silicate, aluminum nitride, and an amino-functional siloxane (a silicone modified to include amino-functional groups). In some embodiments, the amino-functional siloxane may include aminodimethylpolysiloxane.
[0094] In some embodiments, the outer coating 130 includes a single layer or multiple layers, each of which is formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive), as described above. In some embodiments, the outer coating 130 may include a double-layer coating. For example, the outer coating 130 may include a first layer disposed on the conductor layer 120 and a second layer disposed on the first layer. The first layer has a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive) at an operating temperature in the range of 60° C. to 250° C. (e.g., a radiant emissivity greater than 0.75 at a wavelength of about 6 microns at an operating temperature of about 200° C.), thereby facilitating heat radiation from the conductor 100. Additionally, the second layer may have a solar absorptivity of less than 0.5 at wavelengths less than 2.5 microns, thereby reflecting a significant amount of solar radiation on the second layer back into the environment.
[0095] In some embodiments, the first layer of the outer coating 130 can include a microstructure (e.g., any microstructure described herein) configured to provide the first layer with a high radiant emissivity, as described herein. Additionally, the second layer can include nanopores configured to provide the second layer with a high refractive index but low solar absorptivity, as described herein. Each of the first and second layers can be formed of any suitable material as described herein (e.g., PVDF-HFP, PTFE, In some embodiments, the second layer can be similar in structure to the inner coating 116, except that the second layer is formulated or adjusted to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5.
[0096] The outer coating 130 may be applied in the form of a coating or slurry using any suitable method, such as brushing, dipping, spraying, evaporation, post-deposition curing or cross-linking, or shrink wrapping. In some embodiments, for example, the outer surface of the conductor layer 120 (e.g., at least the outermost conductive strands contained in the conductor layer 120) may be cleaned to remove oil, grease, lubricant, dirt, etc. that may be deposited on the conductive strands during the manufacturing process of the conductive strands. The outer surface of the conductive strands of the conductor layer 120 may be cleaned using any suitable method, such as by acid, solvent, or using mechanical means (e.g., sandblasting) to facilitate adhesion of the outer coating 130 to the outer surface of the conductor layer 120. In some embodiments in which the insulating layer 122 is arranged around the conductor layer 120, the outer surface of the insulating layer 122 may be cleaned or textured (e.g., by sandblasting) before the outer coating 130 is deposited on the insulating layer 122. The deposited outer coating 130 may be dried using hot air, infrared drying, or natural drying.
[0097] In some embodiments, the outer coating 130 can provide one or more benefits, such as transparency, conductivity, shorter curing time during coating, high resistance to heat aging, reduced dust accumulation, corrosion resistance, hydrophobicity, ice resistance, weather resistance, scratch and abrasion resistance, wear resistance, flame retardant, self-healing, reduced surface friction, better recoatability, reduced conductor tension, or any combination thereof. In addition, the outer coating 130 can improve the life and performance of the conductor. Hydrophobicity can mean that water droplets on the coating can have a contact angle of about 90° or greater. In some embodiments, hydrophobicity can mean that water droplets on the coating can have a contact angle of about 130° or greater. Self-healing can be activated by exposure to one or more conditions, including normal atmospheric conditions, UV conditions, thermal conditions, or electric field conditions.
[0098] In some other embodiments, the outer coating 130 can be hydrophilic, which minimizes the formation of water droplets because the contact angle is substantially less than 90°. Such implementations may be particularly useful for reducing corona, particularly for extremely high voltage (EHV) and / or ultra-high voltage (UHV) applications where the voltage of the circuit may be greater than 200 kV. Such hydrophilic outer coatings 130 may include, but are not limited to, polyethylene glycol, hydrogels (e.g., silica hydrogels), silica, silicon dioxide, titanium dioxide, polyvinyl alcohol, any other suitable hydrophilic coating, or any suitable combination thereof.
[0099] In some embodiments, in addition to or in lieu of the radiation and emissive properties described herein, outer coating 130 may be a "hard coating" configured to have a hardness, cut resistance, or erosion resistance that is at least 5% greater than that of aluminum or an aluminum alloy. In this way, outer coating 130 may advantageously protect conductor layer 120 (e.g., each of the plurality of conductive strands of conductor layer 120) from erosion, cutting, or other mechanical damage (e.g., from accidental cutting of a kite string).
[0100] In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 5% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 10% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 15% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 20% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 25% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 30% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 40% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 50% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 60% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 70% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 80% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 90% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 130 may have a corrosion resistance that is at least 100% higher than the corrosion resistance of aluminum or an aluminum alloy.
[0101] In some embodiments, the outer coating 130 has a Vickers hardness greater than 175MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 200MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 250MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 300MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 400MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 500MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 600MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 700MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 800MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 900MPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 1GPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 5GPa. In some embodiments, the outer coating 130 has a Vickers hardness greater than 10GPa.
[0102] The hard outer coating 130 may be formed from or include any material that provides erosion resistance or hardness as described herein. In some embodiments, the outer coating 130 can be formed of or include a ceramic, such as a metal oxide (e.g., aluminum oxide, beryllium oxide, cerium oxide, zirconium oxide, etc.), a metal carbide (e.g., calcium carbide, silicon carbide, tungsten carbide, iron carbide, aluminum carbide, beryllium carbide, etc.), a metal boride (e.g., titanium boride, hafnium boride, zirconium boride, vanadium boride, niobium boride, tantalum boride, chromium boride, molybdenum boride, tungsten boride, iron boride, cobalt boride, niobium boride, etc.), a metal nitride (e.g., silicon nitride, zirconium nitride, tungsten nitride, vanadium nitride, tantalum nitride, niobium nitride, etc.), a metal silicide (e.g., chromium silicide, manganese silicide, iron silicide, cobalt silicide, copper silicide, vanadium silicide, magnesium silicide, strontium silicide, calcium silicide, cerium silicide, rhodium silicide, iridium silicide, nickel silicide, ruthenium silicide, etc.), a composite ceramic, a fiber-reinforced ceramic, any other suitable ceramic material, or a combination thereof.
[0103] The hard outer coating 130 can be deposited using any suitable method, such as PVD, CVD, MAO, PAO, spray coating, atomic layer deposition (ALD), or any other suitable coating technique. In some embodiments, the outer coating 130 can be a single layer coating that is formulated to optionally have each of the following: a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. to 250° C., optionally a radiant emissivity of greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns; and an erosion resistance that is at least 5% higher than the erosion resistance of aluminum or an aluminum alloy (e.g., at least about 5% higher, about 6% higher). %, about 7% higher, about 8% higher, about 9% higher, about 10% higher, about 11% higher, about 12% higher, about 13% higher, about 14% higher, about 15% higher, about 16% higher, about 17% higher, about 18% higher, about 19% higher, about 20% higher, about 25% higher, about 30% higher, about 35% higher, about 40% higher, about 45% higher, about 50% higher, about 60% higher, about 70% higher, about 80% higher, about 90% higher, or at least about 100% higher (inclusive)).
[0104] In other embodiments, the outer coating 130 may include a multi-layer coating, wherein each layer of the outer coating 130 provides one or more of radiant emissivity, solar absorptivity, and corrosion resistance in any suitable combination and is arranged on the conductor layer 120 in any suitable order. For example, the first layer of the multi-layer outer coating 130 may optionally have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns, the second layer of the outer coating 130 may optionally have a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60° C. to 250° C., and the third layer may have an corrosion resistance at least 5% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer layer of the outer coating 130 may have an corrosion resistance at least 5% higher than the corrosion resistance of aluminum or an aluminum alloy.
[0105] Figure 2 2 is a side cross-sectional view of a conductor 200 including an outer coating 230 according to an embodiment. The conductor 200 includes a strength member 210, a conductor layer 220, and an outer coating 230, and may optionally further include an insulating layer 222 disposed between the conductor layer 220 and the outer coating 230. The conductor 100 may be used to conduct electricity in a grid transmission application.
[0106] The strength member 210 includes a core 212 and an encapsulation layer 214 arranged circumferentially around the core 212. The core 212 can be formed of a composite material. In some embodiments, the composite material can include a metal-based composite material reinforced by non-metallic fibers, a carbon fiber reinforced composite material with a thermoplastic or thermosetting matrix, or a composite material reinforced with other types of fibers such as quartz, AR glass, E glass, S glass, H glass, silicon carbide, silicon nitride, aluminum oxide, basalt fiber, specially formulated silica fiber, any other suitable composite material or any combination thereof. In some embodiments, the composite material can include a carbon fiber reinforced composite material of a thermoplastic or thermosetting resin. The reinforcement in the composite strength member 212 can be discontinuous, such as whiskers or chopped fibers; or a continuous fiber in a substantially aligned configuration (e.g., parallel to the axial direction) or randomly dispersed (including a spirally wound or interwoven configuration). In some embodiments, the composite material can include a continuous or discontinuous polymer-based composite material reinforced by carbon fibers, glass fibers, quartz or other reinforcing materials, and can also include fillers or additives (e.g., nano additives). In some embodiments, core 212 may include a carbon composite material including a polymer matrix of an epoxy resin cured with an anhydride curing agent. In some embodiments, core 212 may include any material as described with respect to core 112 .
[0107] like Figure 2 As shown in , the core 212 has a generally circular cross-section, but may have any other suitable shape, as described with respect to the core 212. In some embodiments, the core 212 may have a diameter in the range of about 2 mm (inclusive) to about 15 mm (inclusive) (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 mm (inclusive)). In some embodiments, the core 212 may have a glass transition temperature or melting point of at least about 70°C (e.g., at least 75°C, at least 80°C, at least 90°C, at least 100°C, at least 120°C, at least 140°C, at least 150°C, at least 160°C, at least 180°C, at least 200°C, at least 220°C, at least 240°C, or at least 250°C (inclusive)), as described above with respect to the core 212. Although Figure 2 The core 212 is shown as solid, but in some embodiments, the core 212 can be hollow, as described with respect to the core 112. Sensing or transmission components can be embedded in the voids or channels defined in the core 212. For example, in some embodiments, sensors such as strain gauges, accelerometers, or fiber optic sensors can be disposed within or throughout the core 212, as described herein. In some embodiments, the optical fibers that can extend through the core 212 can include communication fibers, as described herein.
[0108] The encapsulation layer 214 is arranged circumferentially around the core 212. The encapsulation layer 214 can be formed of any suitable conductive or non-conductive material. In some embodiments, the encapsulation layer 214 can be formed of a conductive material, including but not limited to aluminum (e.g., 1350-H19), annealed aluminum (e.g., 1350-0), aluminum alloys (e.g., Al-Zr alloys, 6000 series aluminum alloys such as 6201-TSl, -T82, -T83, 7000 series aluminum alloys, 8000 series aluminum alloys, etc.), copper, copper alloys (e.g., copper-magnesium alloys, copper-tin alloys, copper microalloys, etc.), any other suitable conductive material, or any combination thereof, as described with respect to the encapsulation layer 114.
[0109] The encapsulation layer 214 may be disposed on the core 212 using any suitable process. In some embodiments, the encapsulation process for disposing the encapsulation layer 214 around the core 214 includes using a conforming machine or a twisting machine, or any other suitable process as described with respect to the encapsulation layer 214. Figure 2 A single encapsulation layer 214 is shown disposed about the core 212, but in some embodiments, a plurality of encapsulation layers 214 may be disposed about the core 212. In such embodiments, each of the plurality of encapsulation layers 214 may be substantially similar to one another, or may be different from one another (e.g., formed of different materials, having different thicknesses, having different tensile strengths, etc.).
[0110] In some embodiments, the interface between the core 212 and the encapsulation layer 214 may include surface features, such as grooves, slots, cuts, indentations, detents, etc., to enhance adhesion, bonding, and / or interfacial locking between the radially outer surface of the core 212 and the radially inner surface of the encapsulation layer 214. Such surface features can facilitate the retention and preservation of stresses in the encapsulation layer 214 resulting from optional pre-tensioning. In some embodiments, the composite core 212 can have glass fiber tows arranged around its outer surface to form a spiral shape or twisted surface. In some embodiments, a braided or interwoven fiber layer is applied in the outer layer of the core 212 to promote interlocking or bonding between the core 212 and the encapsulation layer 214.
[0111] In some embodiments, the encapsulation layer 214 may have a thickness in the range of about 0.25 mm (inclusive) to about 5 mm (inclusive) or even higher (e.g., 0.25, 0.3, 0.5, 1, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 mm (inclusive), or even higher). In some embodiments, the ratio of the outer diameter of the encapsulation layer 214 to the outer diameter of the core 212 is in the range of about 1.2:1 (inclusive) to about 5:1 (inclusive) (e.g., 1.2:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, or 5:1 (inclusive)).
[0112] In some embodiments, the strength member 210 can have a minimum level of tensile strength, such as at least 600 MPa (e.g., at least 600, at least 700, at least 800, at least 1000, at least 1200, at least 1400, at least 1600, at least 1800, or at least 2000 MPa (inclusive)). In some embodiments, depending on the type of strength member and the degree of reduction in inflection point, the elongation of the strength member 210 during pre-tensioning can include an elongation of at least 0.005% strain (e.g., at least 0.005%, at least 0.01%, at least 0.1%, at least 0.2%, at least 0.25%, at least 0.3%, at least 0.35%, at least 0.4%, at least 0.45%, or at least 0.5% strain (inclusive)), and the strength member 210 can be pre-tensioned before or after entering the conformable machine. In addition, the strength member 210 can be configured to withstand radial compression from crimping of conventional fittings, as well as radial pressure of at least 3 kN (e.g., at least 3 kN, at least 4 kN, at least 5 kN, at least 10 kN, at least 15 kN, at least 20 kN, or at least 25 kN (inclusive)) during conforming during a draw-down process or folding forming.
[0113] In some embodiments, the encapsulation layer 214 may have a smooth and shiny outer surface to maximize the refractive index and reduce the absorptivity (i.e., enhance the reflectivity), thereby reducing the operating temperature of the core 212 and preventing the temperature of the core from exceeding its glass transition temperature or melting point. As further described in detail herein, the outer coating 230 may be formulated to have a high radiative emissivity within the wavelength range of 2.5 microns to 15 microns (inclusive) of solar radiation. Although this may result in cooling of the conductor layer 220, the radiated heat may also propagate toward the strength member 210 and result in heating of the core 212, for example, causing the core 212 to be at a higher operating temperature than the conductor layer 220, which is undesirable. In some embodiments in which there is no twisted layer of conductive material around the encapsulation layer 214, the outer surface of the encapsulation layer 214 (e.g., the inner coating 216 disposed thereon) may be configured to have a high radiative emissivity to remove heat from the conductor 200 by thermal radiation.
[0114] To reduce absorption of such emitted radiation, the outer surface of the encapsulation layer 214 can be sufficiently reflective so as to have an absorptivity of less than 0.5 (e.g., less than 0.5, less than 0.4, less than 0.3, less than 0.2, or less than 0.1) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive) (e.g., 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 11.0, 12.0, 13.0, 14.0, or 15.0 microns (inclusive)) at an operating temperature of the conductor 200 in the range of 90° C. (inclusive) to 250° C. (inclusive) (e.g., 90, 100, 120, 140, 160, 180, 200, 220, 240, or 250° C. (inclusive)). In some embodiments, the outer surface of the encapsulation layer 214 may be surface treated (e.g., plasma treated, textured, etc.) to have an absorptivity as described above. As previously described, a highly reflective encapsulation layer 214 having a low thermal absorptivity may facilitate lowering the operating temperature of the core 212, thereby protecting the core 212 and enabling the conductor 200 to operate at a higher temperature relative to the core 212 so as to inhibit the temperature of the core 212 from exceeding a threshold temperature (e.g., its glass transition temperature or melting point). In some embodiments, the outer surface of the encapsulation layer 214 is configured to have a reflectivity greater than 50% at a thermal radiation wavelength corresponding to an operating temperature greater than 90° C., or a reflectivity as described with respect to the encapsulation layer 114.
[0115] The conductor layer 220 is arranged around the strength member 210 and is configured to transmit electrical signals therethrough at an operating temperature in the range of about 60° C. (inclusive) to 250° C. (inclusive). In some embodiments, the conductor layer 220 may include a plurality of strands of conductive material arranged around the strength member 210, as described with respect to the conductor layer 220. In some embodiments, the conductor layer 220 (e.g., a plurality of strands of conductive material) may include, for example, aluminum, an aluminum alloy, copper, or a copper alloy including a microalloy as a conductive medium, etc. In some embodiments, the conductor layer 220 may include a conductive strand including a Z, C, or S wire to hold the outer strand in place. The conductor layer 220 may have any suitable cross-sectional shape, such as circular, triangular, trapezoidal, etc. In some embodiments, the conductor layer 220 may include a stranded aluminum layer that may be circular or trapezoidal. In some embodiments, the conductor layer 220 may include a Z-shaped aluminum strand. In some embodiments, the conductor layer 220 may include an S-shaped aluminum strand. In various embodiments, the conductor layer 220 may be formed of any suitable material, as described with respect to the conductor layer 120.
[0116] In some embodiments, the strands of conductive material of the conductor layer 220 can be formed using a conformable machine, for example, by extruding a hot, deformable (e.g., semi-solid) conductive material (e.g., aluminum) from a die. The strands can be molded into a circular or trapezoidal shape. In some embodiments, the conductive medium can be extruded from a die or die at an angle to form a conductive strand that is wrapped around the strength member 210 at an angle, as described herein. In some embodiments, the conductor layer 220 may include multiple layers of conductive strands arranged concentrically around the strength member 210. In some embodiments, the conductor layer 220 may optionally be twisted to facilitate the conductor winding around a reel of reasonable size and to facilitate conductor wiring. In some embodiments, the outermost strands contained in the conductor layer 120 may be TW, C, Z, S, or round strands, as described above.
[0117] In some embodiments, conductor 200 may be prestressed, as described above with respect to conductor 100. In some embodiments, conductor layer 220 (e.g., each strand of conductive material contained in conductor layer 220) may include aluminum having an electrical conductivity of at least 50% ICAS, at least 55% ICAS, or at least 60% ICAS or at least 65% ICAS, or may include copper having an electrical conductivity of at least 65% ICAS, at least 75% ICAS, or even at least 95% ICAS. In some embodiments, a metallurgical bond may be provided between strength member 210 and conductor layer 220, for example, by an adhesive. In some embodiments, conductor layer 220 may include aluminum, aluminum alloys, copper and copper alloys, lead, tin, indium tin oxide, silver, gold, non-metallic materials with conductive particles, any other conductive material, conductive alloy, or conductive composite material, or a combination thereof. In some embodiments, conductor layer 220 may include any conductor layer as described in detail with respect to conductor layer 120. In some embodiments, for pure copper, the skin depth of the conductive strands included in the conductor layer 220 may be in the range of 6 mm (inclusive) to about 12 mm (inclusive) at 60 Hz (e.g., 6, 7, 8, 9, 10, 11, or 12 mm (inclusive)), or in the range of about 12 mm (inclusive) to about 20 mm (e.g., 12, 13, 14, or 15 mm (inclusive)) at 25 Hz. For pure aluminum, the skin depth may be in the range of about 9 mm (inclusive) to about 14 mm (inclusive) at 25 Hz (e.g., 9, 10, 11, 12, 13, or 14 mm (inclusive)), and in the range of about 14 mm (inclusive) to about 20 mm (inclusive) at 60 Hz (e.g., 14, 15, 16, 17, 18, 19, or 20 mm (inclusive)). In some embodiments, each conductive strand contained in conductor layer 120 can include copper having a thickness of up to 12 mm (e.g., up to 12, up to 11, up to 10, up to 9, or up to 8 mm, inclusive). In some embodiments, each conductive strand contained in conductor layer 220 can include aluminum having a thickness of up to 16 mm (e.g., up to 16, up to 14, up to 13, up to 12, up to 11, or up to 10 mm, inclusive). In some embodiments, a dielectric coating can be inserted between the conductive strands to optimize the skin effect. In some embodiments, a lubricant can be provided between adjacent conductive strands to facilitate some relative movement of the conductive strands contained in conductor layer 220.
[0118] In some embodiments, an insulating layer 222 (eg, a jacket) may be disposed around the conductor layer 220, such as Figure 2. Insulation layer 222 may be formed of any suitable electrically insulating material, such as rubber, plastic, or polymer (e.g., polyethylene, high-density polyethylene, cross-linked high-density polyethylene, PTFE, etc.). Insulation layer 222 may be configured to electrically isolate or shield conductor 200. In some embodiments, insulation layer 222 may not be included.
[0119] The outer coating 230 is disposed on the outer surface of the conductor layer 220, for example, around the individual strands forming the conductor layer 220, or only on the outer surface of the outermost conductive strands of the conductor layer 220. The outer coating 230 can be formulated to have a solar absorptivity of less than 0.5 (e.g., 0.49, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.1 (inclusive), or even lower) at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and a radiant emissivity of greater than 0.5 (e.g., 0.51, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 (inclusive), or even higher) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive). For example, the outer coating 230 can be formulated to have a radiant emissivity equal to or greater than 0.75 (e.g., 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95 (inclusive), or even higher) at an operating temperature of about 200° C. at a wavelength of about 6 microns and a solar absorptivity less than 0.3 (e.g., 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.15, 0.10 (inclusive), or even lower) at a wavelength of less than 2.5 microns.
[0120] The low solar absorptivity of the outer coating 230 at wavelengths less than 2.5 microns enables the outer coating 230 to reflect a large amount of solar radiation at wavelengths less than 2.5 microns (e.g., greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or even greater than 95% (inclusive) of incident solar radiation), thereby reducing solar absorption and suppressing the increase in the operating temperature of the conductor 200. In addition, the high radiation emissivity of the outer coating 230 at wavelengths in the range of 2.5 microns to 15 microns enables the outer coating 230 to emit the heat generated by the conductor 200 due to the passage of current therein in the form of photons, thereby increasing the radiation of heat from the conductor 200 to the environment, further reducing the operating temperature of the conductor 200. In some embodiments, the outer coating 230 can cause a reduction in the operating temperature of the conductor 200 within a range of about 5° C. (inclusive) to about 40° C. (inclusive) (e.g., 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 25, 30, 35, or 40° C. (inclusive)) at a particular current, as described herein.
[0121] In some embodiments, the unique properties of the outer coating 230 can be caused by including microstructures and nanopores in the outer coating 230. For example, the outer coating 230 can include microstructures with a size in the range of 3 microns (inclusive) to 15 microns (inclusive) (e.g., 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 microns (inclusive)), which are configured to provide the coating with a radiant emissivity greater than 0.5 (e.g., greater than 0.7, 0.7, 0.8, 0.9 or 0.95 (inclusive)), as described above. In some embodiments, the microstructures can include micropores or voids, which can be inherently present in the outer coating 230 or introduced during the manufacturing operation (e.g., ball milling operation) of the outer coating 230.
[0122] In some embodiments, the microstructure may include inorganic particles. For example, the microstructure may include metal oxides, metal nitrides, metal fluorides, metal carbides, metal carbonates and / or rare earth elements. In some embodiments, the microstructure includes CaCO3, such as solid particles, hollow particles and / or core-shell particles. In some embodiments, the microstructure may include silicon dioxide (e.g., porous silicon dioxide or SiO2 spheres randomly distributed in a polymer matrix). In some embodiments, the microstructure may include Al2O3 (e.g., porous alumina) particles, BaSO4 particles or wide bandgap pigments. In some embodiments, the microstructure may include core-shell particles and / or wide bandgap and multi-scale particles that promote reflection of incident sunlight while having vibration modes that provide radiant emissivity in the range of 2.5 microns to 15 microns, as described herein. In some embodiments, the microstructure may include gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide, manganese oxide, chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, tricalcium phosphate, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, magnesium oxide, calcium oxide, any other suitable material, or combinations thereof.
[0123] The outer coating 230 also includes nanopores, nanovoids or nanoholes having a size in the range of about 30 nm (inclusive) to about 700 nm (inclusive) (e.g., 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 25, 300, 350, 400, 450, 500, 550, 600, 650 or 700 nm (inclusive)), which are configured to allow the outer coating 230 to have a solar absorptivity in the range of less than 0.5 (e.g., less than 0.5, 0.4, 0.3, 0.2 or 0.1 (inclusive)). In some embodiments, the outer coating 230 may include fluoropolymers and / or polyurethanes. In some embodiments, the fluoropolymer may include a PVDF-HFP polymer and / or a PVDF-HFP copolymer, or any other suitable material formed using any suitable method as described in detail with respect to outer coating 130 .
[0124] In some embodiments, the outer coating 230 may include PTFE or any other dielectric. In some embodiments, the outer coating 230 may include nanocellulose fibers. In some embodiments, the microstructure may include TiO2 with high emissivity to provide high radiative emissivity of the outer coating 230, and the nanopores contained in the outer coating 230 may provide low solar absorptivity. In some embodiments, the outer coating 230 may also include a color or dye (e.g., a fluorescent dye) to provide limited near infrared and short wave infrared absorption.
[0125] In some embodiments, the outer coating layer 230 may have a thickness T1 of about 50 microns (inclusive) to about 500 microns (inclusive) (e.g., 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, 420, 440, 460, 480, or 500 microns (inclusive)). In some embodiments, before the outer coating layer 230 is applied to the outer surface of the conductor layer 220, a primer, varnish, or adhesive may be applied to the outer surface of the conductor layer 220 (e.g., on each conductive strand forming the conductor layer 220, only on the outermost conductive strand forming the conductor layer 220, or on the outer surface of the insulating layer 222). In some embodiments, the primer and / or outer coating 230 may be hydrophobic, for example, to inhibit ice formation, inhibit scaling, prevent ultraviolet radiation, and inhibit waterborne fouling. In some embodiments, the outer surface of at least a portion of the conductive strands forming the conductor layer 220 may be cleaned, for example, using a surfactant or solvent, to provide a clean surface prior to depositing the outer coating 230 thereon. In some embodiments, the outer surface of the conductor layer 220 (e.g., the outer surface of each strand, the outermost strand, or the outermost strand forming the conductor layer 220) or the insulating layer 222 may be roughened by sandblasting to provide a rough surface to facilitate adhesion of the outer coating 230 thereto.
[0126] In some embodiments, the outer coating 230 can be hydrophilic, for example, to minimize corona in EHV and UHV applications where the circuit voltage is greater than 200 kV (e.g., a typical corona excitation initiation voltage). Such hydrophilic outer coating 130 can include, but is not limited to, polyethylene glycol, hydrogel (e.g., silica hydrogel), silica, silicon dioxide, titanium dioxide, polyvinyl alcohol, any other suitable hydrophilic coating, or any suitable combination thereof.
[0127] In some embodiments, the outer coating 230 may include a coating having a resin matrix, such as a black coating, such as a polyurethane coating, and may optionally include ceramic particles. In some embodiments, the outer coating 230 may include a suitable fluorine-containing copolymer compound of about 50% (inclusive) to about 99% (inclusive) by dry weight (for example, about 75% (inclusive) to about 95% (inclusive) by dry weight). In some embodiments, the outer coating 230 may include a polymer cross-linked by any suitable method, which includes, for example, moisture curing, chemical curing, thermal curing, UV curing, and electron beam curing methods. The cross-linking agent may include, but is not limited to, a cross-linking agent reactive to hydroxyl, acid, epoxide, amine, cyanate ester of a monomer or oligomer or polymer in liquid, semi-solid or powder form, which has a urethane, fluorine, silane, fluorosilane, fluorosilicone, silsesquioxane, polytetrafluoroethylene ("PTFE"), epoxy, phenol, ether, silicone or acrylic group in the main chain or grafted alone or in combination with other functional groups. Suitable chemical crosslinking agents (e.g., reactants) may include monomers or oligomeric polymer resins that can promote the curing of the composition when mixed with a crosslinkable fluorinated copolymer. In some embodiments, the crosslinking agent may include acrylates, fluorosilanes, fluorosilicones, methacrylates, silanes (including methoxysilanes and epoxysilanes) metal catalysts, triallyl isocyanurate ("TAIC"), peroxides, or combinations thereof. In some embodiments, the fluorinated copolymer may, for example, have hydroxyl groups that can be crosslinked with a polyisocyanate crosslinker such as hexamethylene-6,6-diisocyanate ("HDI"). Such HDI crosslinkers may be aromatic or aliphatic. In certain embodiments, a catalyst may be additionally included to accelerate the crosslinking reaction. A suitable crosslinking agent may be included in an amount of about 1% (inclusive) to about 20% (inclusive) of the outer coating 230 by dry weight.
[0128] In some embodiments, the outer coating 230 may include additional components, such as one or more fillers (e.g., microstructures), solvents, defoamers, emulsifiers, thickeners, UV and light stabilizers, or resins. In some embodiments, the outer coating 230 may include metal oxides, metal nitrides, metal fluorides, rare earth elements, and metal carbides, such as, but not limited to, gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide ("silica"), chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, HfO2, and combinations thereof.
[0129] In some embodiments, suitable rare earth materials may include one or more of rare earth oxides, rare earth carbides, rare earth nitrides, rare earth fluorides, or rare earth borides. Examples of rare earth oxides include scandium oxide, yttrium oxide, lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, thulium oxide, ytterbium oxide, and lutetium oxide. Examples of rare earth carbides include, but are not limited to, scandium carbide, yttrium carbide, cerium carbide, praseodymium carbide, neodymium carbide, samarium carbide, europium carbide, gadolinium carbide, terbium carbide, dysprosium carbide, holmium carbide, erbium carbide, thulium carbide, ytterbium carbide, and lutetium carbide. Examples of rare earth fluorides include, but are not limited to, scandium fluoride, yttrium fluoride, cerium fluoride, praseodymium fluoride, neodymium fluoride, samarium fluoride, europium fluoride, gadolinium fluoride, terbium fluoride, dysprosium fluoride, holmium fluoride, erbium fluoride, thulium fluoride, ytterbium fluoride, and lutetium fluoride. Examples of rare earth borides include, but are not limited to, scandium boride, yttrium boride, lanthanum boride, cerium boride, praseodymium boride, neodymium boride, samarium boride, europium boride, gadolinium boride, terbium boride, dysprosium boride, holmium boride, erbium boride, thulium boride, ytterbium boride, and lutetium boride.
[0130] In some embodiments, the filler may also include conductive fillers, including carbon nanotubes, graphene and graphite. In some embodiments, the filler may have an average particle size of about 25 microns or less (e.g., about 10 microns or less, or about 500 nanometers or less). The coating may optionally contain less than about 50% by weight (e.g., about 2% (inclusive) to about 30% (inclusive) by weight, or about 5% (inclusive) to about 20% (inclusive) by weight) of suitable fillers. In some embodiments, the outer coating 230 may include a defoamer, for example, to inhibit or delay the formation of foam (e.g., when water is added to the heat-resistant coating composition). Suitable examples of defoamers may include silicon-based defoamers and non-silicon-based defoamers. In some embodiments, surfactants may also be used as defoamers. Suitable surfactants include, but are not limited to, cationic, anionic or nonionic surfactants and fatty acid salts. In some embodiments, the defoamer may be about 0.1% (inclusive) to about 5% (inclusive) of the outer coating 230 by weight.
[0131] In some embodiments, the outer coating 230 may include, for example, an emulsifier to maintain a uniform dispersion of the compound in the aqueous solution. Suitable emulsifiers may include, but are not limited to, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, potassium stearate, sodium dioctyl sulfosuccinate, dodecyl diphenoxy disulfonate, nonylphenoxyethyl poly (1) ethoxyethyl ammonium sulfate, sodium styrene sulfonate, sodium dodecyl allyl succinate sulfonate, linseed oil fatty acid, sodium or ammonium salt of ethoxylated nonylphenol phosphate, sodium octoxynol-3-sulfonate, sodium coconut creatine, sodium 1-alkoxy-2-hydroxypropyl sulfonate, α-olefin (C 14 -C 16) sodium sulfonate, hydroxyalkanol sulfate, N-(1,2-dicarboxyethyl)-N-octadecylsulfosalicylic acid amine tetrasodium salt, N-octadecylsulfosalicylamino acid disodium salt, alkylamidopolyethoxysulfosuccinate disodium, ethoxylated nonylphenolsulfosuccinate half ester disodium, ethoxyethyl sodium sulfate. The outer coating 230 may contain an emulsifier in an amount ranging from about 2% (inclusive) to about 3% (inclusive) by weight of the outer coating 230.
[0132] In some embodiments, a coalescing agent or thickener may be added to improve the formation of a thin film on the outer coating 230. In such embodiments, a coalescing agent may be included that is about 20% or less by weight of the coating composition (e.g., in the range of about 2% (inclusive) to about 10% (inclusive) by weight). In certain embodiments, a UV or light stabilizer may be added to the outer coating 230 to improve external weather resistance. Suitable UV or light stabilizers may include benzotriazole-type, triazine-type UV absorbers and HALS compounds. In the outer coating 230, about 0.1% (inclusive) to about 5% (inclusive) by weight of UV or light stabilizers may be included. Additional resins may be included in the outer coating 230 to improve the performance of the outer coating 230. For example, one or more acrylic, silicone, polyurethane, silane, fluorosilane, silsesquioxane or epoxy resins may be added to the outer coating 230. Alternatively or additionally, commercial lubricants, waxes and friction reducers may be added to the coating composition. Such resins can improve various properties of the composition, including, for example, processability, durability and service life of the coating. In the coating composition, about 0.1% to about 40% by weight, inclusive, of a suitable resin may be included.
[0133] In some embodiments, one or more binders may be included in the outer coating 230, for example, in the range of about 10% to about 70% (for example, about 10% to 20%, about 20% to 30%, about 30% to 40%, about 40% to 50%, about 50% to 60%, or about 60% to 70%) based on the total weight of the dry ingredients of the outer coating 230. The binder may include functional groups such as hydroxyl, epoxy, amine, acid, cyanate, silicate, silicate, ether, carbonate, maleic acid, methyltrimethoxysilane, etc. The inorganic binder may be, but is not limited to, metal silicates such as potassium silicate, sodium silicate, lithium silicate, and magnesium aluminum silicate; peptized monohydrated alumina; colloidal silica; colloidal alumina, aluminum phosphate, and combinations thereof.
[0134] In some embodiments, one or more reflective additives may also be included in the outer coating 230. Such reflective additives may include, but are not limited to, cobalt, aluminum, bismuth, lanthanum, lithium, magnesium, neodymium, niobium, vanadium, iron, chromium, zinc, titanium, manganese, and nickel-based metal oxides and ceramics. The reflective additive may be included in a concentration of about 0.1% (inclusive) to about 5% (inclusive) (by the total weight of the dry ingredients) alone or mixed with a colorant. In some embodiments, one or more stabilizers may be included in the outer coating 230, for example, in a concentration of about 0.1% (inclusive) to about 2% (inclusive) (by the total weight of the dry ingredients). Examples of stabilizers include, but are not limited to, dispersion stabilizers, such as bentonite.
[0135] In some embodiments, in the outer coating 230, one or more colorants may be included, for example, at a concentration of about 0.02% (inclusive) to 0.2% (inclusive) (based on the total weight of dry ingredients). The colorant may be an organic or inorganic pigment, including but not limited to titanium dioxide, rutile, titanium, anatase, brookite, cadmium yellow, cadmium red, cadmium green, orange cobalt, cobalt blue, cyan blue, golden yellow, cobalt yellow, copper pigment, azurite, Han purple, Han blue, Egyptian blue, malachite, Paris green, phthalocyanine blue BN, phthalocyanine green G, verdigris, chrome green, iron oxide pigment, blood red, mummy brown, red oxide, red ochre, Venetian red, Prussian blue, clay pigment, yellow ochre, raw ochre, burnt ochre, raw umber, burnt umber, marine pigment (ultramarine, ultramarine green), zinc pigment (zinc white, zinc ferrite) and combinations thereof. In some embodiments, the outer coating 230 may contain less than about 5% of organic material. For example, the coating composition may include sodium silicate, aluminum nitride, and an amino-functional siloxane (a silicone modified to include amino-functional groups). In some embodiments, the amino-functional siloxane may include aminodimethylpolysiloxane.
[0136] The outer coating 230 may be applied in the form of a paint or slurry using any suitable method, such as brushing, dipping, spraying, evaporation, post-deposition curing or cross-linking, or shrink wrapping. In some embodiments, for example, the outer surface of the conductor layer 220 (e.g., at least the outermost conductive strands contained in the conductor layer 220) may be cleaned to remove oil, grease, lubricant, dirt, etc. that may be deposited on the conductive strands during the manufacturing process of the conductive strands. The outer surface of the conductive strands of the conductor layer 220 may be cleaned using any suitable method, such as by acid, solvent, or using mechanical means (e.g., sandblasting) to facilitate adhesion of the outer coating 230 to the outer surface of the conductor layer 220. In some embodiments in which the insulating layer 222 is arranged around the conductor layer 220, the outer surface of the insulating layer 222 may be cleaned or textured (e.g., by sandblasting) before the outer coating 230 is deposited on the insulating layer 222. The deposited outer coating 230 may be dried using hot air or dried naturally. In some embodiments, the outer surface of conductor layer 220 may be treated or otherwise configured to have an absorptivity of less than 50% corresponding to an operating temperature greater than 90 degrees, as described with respect to conductor layer 120 .
[0137] In some embodiments, in addition to or in lieu of the radiation and emission properties described herein, outer coating 230 can be a hard coating configured to have a hardness, cut resistance, or erosion resistance that is at least 5% higher than that of aluminum or an aluminum alloy. In this way, outer coating 230 can advantageously protect conductor layer 220 (e.g., each of the plurality of conductive strands of conductor layer 220) from erosion, cutting, or other mechanical damage (e.g., from accidental cutting of a kite string).
[0138] In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 5% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 10% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 15% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 20% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 25% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 30% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 40% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 50% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 60% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 70% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 80% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 90% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer coating 230 may have a corrosion resistance that is at least 100% higher than the corrosion resistance of aluminum or an aluminum alloy.
[0139] In some embodiments, the outer coating 230 has a Vickers hardness greater than 175 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 250 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 250 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 300 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 400 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 500 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 600 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 700 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 800 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 900 MPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 1 GPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 5 GPa. In some embodiments, the outer coating 230 has a Vickers hardness greater than 10 GPa.
[0140] The hard outer coating 230 may be formed from or include any material that provides erosion resistance or hardness as described herein. In some embodiments, the outer coating 230 can be formed of or include a ceramic, such as a metal oxide (e.g., aluminum oxide, beryllium oxide, cerium oxide, zirconium oxide, etc.), a metal carbide (e.g., calcium carbide, silicon carbide, tungsten carbide, iron carbide, aluminum carbide, beryllium carbide, etc.), a metal boride (e.g., titanium boride, hafnium boride, zirconium boride, vanadium boride, niobium boride, tantalum boride, chromium boride, molybdenum boride, tungsten boride, iron boride, cobalt boride, Nb boride, etc.), a metal nitride (e.g., silicon nitride, zirconium nitride, tungsten nitride, vanadium nitride, tantalum nitride, niobium nitride, etc.), a metal silicide (e.g., chromium silicide, manganese silicide, iron silicide, cobalt silicide, copper silicide, vanadium silicide, magnesium silicide, strontium silicide, calcium silicide, cerium silicide, rhodium silicide, iridium silicide, nickel silicide, ruthenium silicide, etc.), a composite ceramic, a fiber-reinforced ceramic, any other suitable ceramic material, or a combination thereof.
[0141] The hard outer coating 230 may be deposited using any suitable method, such as PVD, CVD, MAO, PAO, spraying, ALD, or any other suitable coating technique. In some embodiments, the outer coating 230 may be a single layer coating that is formulated to have each of the following: a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. to 250° C., a radiant emissivity of greater than 0.5 at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive), and an erosion resistance at least 5% greater than the erosion resistance of aluminum or an aluminum alloy. In other embodiments, the outer coating 230 may include a multilayer coating, wherein each layer of the outer coating 230 provides one or more of radiant emissivity, solar absorptivity, and erosion resistance in any suitable combination and is disposed on the conductor layer 220 in any suitable order. For example, the first layer of the multi-layer outer coating 230 may have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns, the second layer of the outer coating 230 may have a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60° C. to 250° C., and the third layer of the outer coating 230 may have a corrosion resistance at least 5% higher than the corrosion resistance of aluminum or an aluminum alloy. In some embodiments, the outer layer of the outer coating 230 may have a corrosion resistance at least 5% higher than the corrosion resistance of the aluminum or aluminum alloy that may be used to form the conductor layer 220. In various embodiments, the corrosion resistance of the aluminum or aluminum alloy that may be used to form the conductor layer 220 may be 1 micron / hour (inclusive) to 10 mm / hour (inclusive), and the outer coating 230 may be configured to have a corrosion resistance at least 5% higher than the aluminum or aluminum alloy used to form the conductor layer 220.
[0142] Figure 33 is a side cross-sectional view of a conductor 300 according to an embodiment. The conductor 300 is similar to the conductor 200, for example, the conductor 300 includes a strength member 310, the strength member 310 includes a core 312 and an encapsulation layer 314, the core 312 and the encapsulation layer 314 can be respectively substantially similar to the core 112, 212 and the encapsulation layer 114, 214 as described above, and therefore will not be described in further detail herein. The conductor 300 also includes a conductor layer 320 arranged around the strength member 310, and has an outer coating 330 arranged around the conductor layer 320. The conductor layer 320 and the outer coating 330 can be substantially similar to the conductor layer 120, 220 and the outer coating 130, 230 described above, and therefore will not be described in further detail herein. Although not shown, in some embodiments, as described above, an insulating layer (e.g., insulating layer 222) can be inserted between the outer coating 330 and the conductor layer 320.
[0143] Unlike the conductor 200 , the conductor 300 further includes an inner coating layer 316 disposed on an outer surface of the encapsulation layer 314 (eg, interposed between the encapsulation layer 314 and the conductor layer 320 ). In some embodiments, the inner coating 316 can be formulated to have an absorptivity (i.e., thermal absorptivity) of less than 0.5 (e.g., less than 0.5, less than 0.4, less than 0.3, less than 0.2, or less than 0.1) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive) (e.g., 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 11.0, 12.0, 13.0, 14.0, or 15.0 microns (inclusive)) at an operating temperature of the conductor 300 in the range of 90° C. (inclusive) to 250° C. (inclusive) (e.g., 90, 100, 120, 140, 160, 180, 200, 220, 240, or 250° C. (inclusive)). Thus, the inner coating 316 can be configured to reflect a significant amount of thermal radiation having a wavelength equal to or less than 2.5 microns that is incident to the inner coating 316 due to the heat generated by the conductor layer 320 (e.g., at least 50% of the radiation having a wavelength equal to or less than 2.5 microns that is incident to the encapsulation layer 314). In some embodiments, the thickness of the inner coating 316 can be in the range of 1 micron (inclusive) to 500 microns (inclusive) (e.g., 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, or 500 microns (inclusive)). The coating on the core surface or the encapsulation layer 314 surface can be non-conductive or poorly conductive, such as comprising ceramic, to minimize conductive heat transfer between the passively heated composite core 312 and the electrically conductive encapsulation layer 314 metal having resistive heating.
[0144] In some embodiments, the inner coating 316 may include nanopores, such as voids or holes having a size equal to or less than 500 nm (e.g., 10 nm (inclusive) to 500 nm (inclusive)), so that the inner coating 316 has an absorptivity of less than 0.5, as described herein. The inner coating 316 may be formed of any suitable material and include any suitable additives so that the inner coating 316 has an absorptivity of less than 0.5 microns, as described herein. In some embodiments, the inner coating 316 may include a binder and a reflector. In some embodiments, the inner coating 316 may also include a filler, a stabilizer, a colorant, a surfactant, and a reflector configured to enhance thermal reflection in the range of 2.5 microns to 15 microns. In some embodiments, the inner coating 316 may include an inorganic material and may be substantially free of organic material (e.g., having less than 10% organic material).
[0145] In some embodiments, the concentration of the binder in the inner coating 316 can be in the range of 20% (inclusive) to 60% (inclusive). In some embodiments, the binder can include functional groups such as hydroxyl, epoxy, amine, acid, cyanate, silicate, silicate, ether, carbonate, maleic acid, etc. Inorganic binders can include, but are not limited to, metal silicates such as potassium silicate, sodium silicate, lithium silicate and magnesium aluminum silicate, peptized monohydrated alumina, colloidal silica, colloidal alumina, aluminum phosphate and combinations thereof. In some embodiments, the inner coating 316 can include one or more reflective additives, including but not limited to cobalt, aluminum, bismuth, lanthanum, lithium, magnesium, neodymium, niobium, vanadium, iron, chromium, zinc, titanium, manganese and nickel-based metal oxides and ceramics. In some embodiments, the reflective additive can be used alone or in combination with a colorant, with a concentration in the range of about 0.1% (inclusive) to about 5% (inclusive) (by the total weight of the dry ingredients of the inner coating).
[0146] In some embodiments, one or more stabilizers may be included in the inner coating 316, for example, at a concentration in the range of about 0.1% to about 2% (by total weight of dry ingredients). Examples of stabilizers include, but are not limited to, dispersion stabilizers such as bentonite. One or more colorants may be used in the inner coating 316, for example, at a concentration in the range of about 0.02% (inclusive) to 0.2% (inclusive) (by total weight of dry ingredients). The colorant can be an organic or inorganic pigment, including but not limited to titanium dioxide, rutile, titanium, anatase, brookite, cadmium yellow, cadmium red, cadmium green, orange cobalt, cobalt blue, cyan blue, golden yellow, cobalt yellow, copper pigment, azurite, Han purple, Han blue, Egyptian blue, malachite, Paris green, phthalocyanine blue BN, phthalocyanine green G, verdigris, chrome green, iron oxide pigment, blood red, mummy brown, red oxide, red ochre, Venetian red, Prussian blue, clay pigment, yellow ochre, raw ochre, burnt ochre, raw brown, burnt brown, marine pigment (ultramarine, ultramarine green), zinc pigment (zinc white, zinc ferrite) and combinations thereof. In some embodiments, one or more surfactants can also be used in the inner coating 316, for example, in a concentration of about 0.05% (inclusive) to about 0.5% (inclusive) (by the total weight of dry ingredients). Suitable surfactants include but are not limited to cationic, anionic or nonionic surfactants and fatty acid salts.
[0147] In some embodiments, the inner coating 316 may include Polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF), copolymers or any suitable combination thereof, these materials can be formulated into coatings and can include additives to increase reflectivity, i.e., reduce the absorptivity in the range of 2.5 microns to 15 microns. In some embodiments, the inner coating 316 may include polyvinylidene fluoride-hexafluoropropylene copolymer) (PVDF-HFP), whose nanoporosity is in the range of 50% or more, resulting in the inner coating 316 having a solar absorptivity of less than 0.5 at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive) at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), as described previously herein. In some embodiments, the inner coating 316 may include nanocellulose fibers having a mesoporous structure. In some embodiments, the inner coating 316 may include alumina, SiO2, and porous PTFE.
[0148] In some embodiments, the inner coating 316 may include particles, for example, core-shell particles having a wide bandgap configured to reduce absorptivity. Such particles may include particles of inorganic materials such as Al2O3, BaSO4, etc. In some embodiments, the inner coating 316 may include PVDF-HFP, which may be dissolved in a small amount of solvent (e.g., acetone) in, for example, a ball milling operation, and then dissolved in water, so that the inner coating 316 has nanopores in the range of about 10nm (inclusive) to about 500nm (inclusive) (e.g., 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, or 500nm (inclusive)). In some embodiments, the inner coating 316 may include one or more layers of silicon, ZnO, HfO2, TiO2, MgF2, Si3N4, Ta2O5, and / or ZnO2. In some embodiments, the inner coating 316 may include silver.
[0149] In some embodiments, the thickness T2 of the inner coating 316 may be in the range of 50 microns (inclusive) to 300 microns (inclusive) (e.g., 50, 100, 150, 200, 250, or 300 microns (inclusive)). In some embodiments, the ratio of the thickness T1 of the outer coating 330 to the thickness T2 of the inner coating 316 may be in the range of about 1:1 (inclusive) to about 10:1 (inclusive) (e.g., 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1 (inclusive)).
[0150] In some embodiments, a primer, varnish, or adhesive of a coating may be applied to the outer surface of the encapsulation layer 314 to facilitate adhesion of the inner coating 316 to the encapsulation layer 314. The inner coating 316 may be applied in the form of a coating or slurry using any suitable method, such as brushing, dipping, spraying, evaporation, post-deposition curing or cross-linking, or shrink wrapping. In some embodiments, the outer surface of the encapsulation layer 314 may be cleaned, for example, by a solvent or using mechanical means (e.g., sandblasting) to facilitate adhesion of the inner coating 316 to the outer surface of the encapsulation layer 314. In some embodiments, the inner coating 316 may also be optionally disposed on the inner surface of the conductor layer 320 (e.g., the inner surface of a portion of the conductive strands included in the conductor layer 320 disposed proximate to the outer surface of the encapsulation layer 314). In some embodiments, the inner coating 316 may be substantially durable, tough, and / or scratch-resistant so as to protect the outer surface of the encapsulation layer 314 from damage, for example, during installation of the conductor layer 320 around the strength member 310.
[0151] Figure 4is a schematic diagram of a coating 430 for coating a conductor (eg, an outer layer of the conductor layer 120, 220, 320 of the conductor 100, 200, 300) according to an embodiment, the coating 430 having a high refractive index, low solar absorptivity, and high radiation emissivity. The coating 430 may be formulated to have a solar absorptivity of less than 0.5 (e.g., 0.49, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.1 (inclusive), or even lower) at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and a radiant emissivity greater than 0.5 (e.g., 0.51, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 (inclusive), or even higher) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive). For example, coating 430 can be formulated to have a radiant emissivity equal to or greater than 0.75 (e.g., 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95 (inclusive), or even higher) at an operating temperature of about 200° C. at a wavelength of about 6 microns and a solar absorptivity less than 0.3 (e.g., 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.15, 0.10 (inclusive), or even lower) at a wavelength of less than 2.5 microns. In some embodiments, the outer coating 430 can cause a reduction in the operating temperature of the conductor at a particular current in the range of 5° C. (inclusive) to about 40° C. (inclusive) (e.g., 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 25, 30, 35, or 40° C. (inclusive)), as described herein.
[0152] In some embodiments, coating 430 may include a fluoropolymer and / or a polyurethane. In some embodiments, the fluoropolymer may include a PVDF-HFP polymer and / or a PVDF-HFP copolymer, or any other suitable material formed using any suitable method as described in detail with respect to coating 130. In some embodiments, outer coating 430 may include PTFE or any other dielectric. In some embodiments, outer coating 430 may include nanocellulose fibers. In some embodiments, outer coating 430 may include a coating having a resin matrix, such as a black coating, such as a polyurethane coating. In some embodiments, coating 430 may include a suitable fluorine copolymer compound of about 50% (inclusive) to about 99% (inclusive) by dry weight (e.g., about 75% (inclusive) to about 95% (inclusive) by dry weight). In some embodiments, coating 430 may include a hydrophilic coating, for example, any hydrophilic coating described in detail about outer coating 130 or 230.
[0153] In some embodiments, coating 430 may include a polymer cross-linked by any suitable method, including, for example, moisture curing, chemical curing, thermal curing, UV curing, and electron beam curing methods. Cross-linking agents may include, but are not limited to, cross-linking agents reactive to hydroxyl groups, acids, epoxides, amines, cyanates, monomers or oligomers or polymers in liquid, semi-solid or powder form, having urethane, fluorine, silane, fluorosilane, fluorosilicone, silsesquioxane, polytetrafluoroethylene, epoxy, phenol, ether, silicone or acrylic groups grafted in the main chain or individually or in combination with other functional groups. Suitable chemical cross-linking agents (e.g., reactants) may include monomers or oligomeric polymer resins that can promote the curing of the composition when mixed with cross-linkable fluorinated copolymers.
[0154] In some embodiments, the crosslinking agent may include acrylates, fluorosilanes, fluorosilicones, methacrylates, silanes (including methoxysilanes and epoxysilanes) metal catalysts, triallyl isocyanurate ("TAIC"), peroxides, or combinations thereof. In some embodiments, the fluorinated copolymer may have hydroxyl groups that can be crosslinked with a polyisocyanate crosslinker such as hexamethylene-6,6-diisocyanate ("HDI"). Such HDI agents may be aromatic or aliphatic. In certain embodiments, a catalyst may be additionally included to accelerate the crosslinking reaction. A suitable crosslinking agent may be included in an amount of about 1% (inclusive) to about 20% (inclusive) of the coating 430 by dry weight.
[0155] The coating 430 may include microstructures 432 and nanopores 434 arranged or formed throughout the volume of the coating 430. For example, the coating 430 may include microstructures 432 having a size in the range of 3 micrometers (inclusive) to 15 micrometers (inclusive) (e.g., 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 micrometers (inclusive)), which are configured to give the coating a radiation emissivity greater than 0.5 (e.g., greater than 0.7, 0.7, 0.8, 0.9, or 0.95 (inclusive)), as previously described. In some embodiments, the microstructures 432 may include micropores or voids that may be inherently present in the coating 430 or introduced during a manufacturing operation (e.g., a ball milling operation) of the outer coating 430. The tailored microstructures 432 may maximize the refractive index for a wavelength of interest (i.e., a wavelength at or near 6 micrometers in thermal radiation at a temperature of, for example, close to 200°C).
[0156] In some embodiments, the microstructure 432 may include inorganic particles. For example, the microstructure 432 may include metal oxides, metal nitrides, metal fluorides, metal carbides, metal carbonates and / or rare earth elements, for example, as described with respect to the outer coating 130, 230. In some embodiments, the microstructure 432 may include CaCO3, such as solid particles, hollow particles and / or core-shell particles. In some embodiments, the microstructure 432 may include silicon dioxide (e.g., porous silicon dioxide or SiO2 spheres randomly distributed in a polymer matrix). In some embodiments, the microstructure 432 may include Al2O3 (e.g., porous alumina) particles, BaSO4 particles, or wide bandgap pigments. In some embodiments, the microstructure 432 may include core-shell particles and / or wide bandgap and multi-scale particles that promote reflection of incident sunlight while having a vibration mode that provides radiant emissivity in the range of 2.5 microns to 15 microns, as described herein. In some embodiments, microstructure 432 may include gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide, manganese oxide, chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, tricalcium phosphate, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, magnesium oxide, calcium oxide, any other suitable material, or any combination thereof, and may optionally include any other ceramic particles as described herein.
[0157] In some embodiments, microstructure 432 may include metal oxides, metal nitrides, metal fluorides, rare earth elements, and metal carbides, such as, but not limited to, gallium oxide, cerium oxide, zirconium oxide, silicon hexaboride, carbon tetraboride, silicon tetraboride, silicon carbide, molybdenum disilicide, tungsten disilicide, zirconium diboride, zinc oxide, copper chromite, magnesium oxide, silicon dioxide ("silica"), chromium oxide, iron oxide, boron carbide, boron silicide, copper chromium oxide, titanium dioxide, aluminum nitride, boron nitride, aluminum oxide, HfO2, and combinations thereof. Certain fillers, such as, for example, including boron oxide, zinc oxide, cerium oxide, silicon dioxide, and titanium dioxide, may act as emissives to improve the radiation of heat from the coating.
[0158] The outer coating 430 also includes nanopores 434 (e.g., nanovoids or nanoholes) having a size in the range of about 30 nm (inclusive) to about 700 nm (inclusive) (e.g., 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 25, 300, 350, 400, 450, 500, 550, 600, 650, or 700 nm (inclusive)), which are configured to provide the outer coating 430 with a solar absorptivity in the range of less than 0.5 (e.g., less than 0.5, 0.4, 0.3, 0.2, or 0.1 (inclusive)). The customized microstructure 434 can maximize the refractive index for the wavelength of interest (i.e., wavelengths at or near about 0.5 microns in the solar absorptivity).
[0159] In some embodiments, coating 430 may include additional components, such as one or more fillers (e.g., microstructures), solvents, defoamers, emulsifiers, thickeners, UV and light stabilizers, dyes, or resins, as described in detail with respect to outer coating 130, 230, or 330.
[0160] In some embodiments, coating 430 may include, for example, one or more binders in the range of about 10% to about 70% (for example, about 10% to 20%, about 20% to about 30%, about 30% to about 40%, about 40% to about 50%, about 50% to about 60%, about 60% to about 70%) based on the total weight of the dry ingredients of outer coating 130. The binder may include any binder as described with respect to coatings 130, 230, 330. In some embodiments, coating 430 may include one or more reflective additives, stabilizers, dyes, colorants, pigments.
[0161] Figure 5Schematic diagram of a multilayer coating 530 with low solar absorptivity and high radiant emissivity for coating a conductor (e.g., conductor 100, 200, 300) according to an embodiment. The outer coating 530 may include a first layer 531 configured to be disposed on the outer surface of the conductor layer (e.g., conductor layer 120, 220, 320), and a second layer 533 disposed on the first layer 531. The first layer 531 may have a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive) at an operating temperature in the range of 60° C. to 250° C. (e.g., a radiant emissivity greater than 0.75 at a wavelength of about 6 microns at an operating temperature of about 200° C.), thereby facilitating heat radiation from the conductor (e.g., conductor 100, 200, 300). In addition, the second layer 533 can have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns at an operating temperature in the range of 60°C to 250°C (for example, a solar absorptivity of less than 0.3 at a wavelength less than 2.5 microns at an operating temperature of about 200°C), thereby reflecting a large amount of solar radiation on the second layer back into the environment.
[0162] In some embodiments, the first layer 531 of the outer coating 530 can include a microstructure (e.g., any of the microstructures described herein with respect to the outer coatings 130, 230, 330, 430) configured to provide the first layer 531 with a high radiant emissivity, as described herein. In addition, the second layer 533 can include nanopores (e.g., as described with respect to the outer coatings 130, 230, 330, 430) configured to provide the second layer 532 with a low solar absorptivity, as described herein. The first layer 531 and the second layer 533 can both be formed of any suitable material as described herein (e.g., PVDF-HFP, PTFE, In some embodiments, the second layer 533 can be similar in structure to the inner coating 116, 416, except that the second layer 533 is formulated or adjusted to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5.
[0163] In some embodiments, the first layer 531 and / or the second layer 533 can be formulated to also have an erosion resistance that is at least 5% higher than the erosion resistance of aluminum or an aluminum alloy (e.g., having a Vickers hardness greater than about 175 MPa, as described in detail with respect to the outer coating 130, 230). For example, the first layer 531 and / or the second layer 533 can include a ceramic (e.g., any ceramic as described with respect to the outer coating 130, 230). In some embodiments, the outer coating 530 can be a three-layer coating, i.e., Figure 5, optionally including a third layer 535 disposed on the second layer 533. The third layer 535 may have an erosion resistance at least 5% higher than that of aluminum or an aluminum alloy, and may have a Vickers hardness greater than about 175 MPa (e.g., as described in detail with respect to the outer coating 130, 230). In some embodiments, the third layer 535 may be the outermost layer of the outer coating 530. In some embodiments, the third layer 535 may be the innermost layer of the outer coating 530. In some embodiments, the third layer 535 may be disposed between the first layer 531 and the second layer 533.
[0164] Fig. 6A 6 is a side cross-sectional view of a coupler or fitting 640a crimped to an axial end of a conductor 600a and coated with a coating 630a having low solar absorptivity and high radiant emissivity in accordance with an embodiment. In some embodiments, the coupler 640a may include a closed-end coupler configured to couple the axial end of the conductor 600a to a tensioning tower or pole. The conductor 600a includes a strength member 610a and a conductor layer 620a disposed about the strength member 610a, the strength member 610a including a core 612a and an encapsulation layer 614a. The strength member 610a and the conductor layer 620a may be substantially similar to the strength member 110 or 210 and the conductor layer 120 or 220, and thus will not be described in further detail herein.
[0165] The conductor layer 620a of the conductor 600a may also be coated with a coating 630a. Before coupling the coupler 640a to the conductor 600a, a portion of the coating 630a disposed at the axial end of the conductor layer 620b inserted into the coupler 640a may be removed from the conductor layer 620a. For example, the coating 630a disposed on the conductor layer 620a may be electrically insulating, and for the current passing through the conductor layer 620a, it is desirable that it also passes through the coupler 640a. Removing the electrically insulating coating from the corresponding axial end of the conductor layer 620a may allow the inner surface of the coupler 640a to directly contact the conductor layer 620a when the conductor 600a is coupled to the coupler 640a, thereby achieving electrical transfer between the conductor layer 620a and the coupler 640a. The portion of the outer coating 630a arranged at the axial end of the conductor layer 620a can be removed using any suitable method, including but not limited to physical removal (e.g., using a brush, peeler, grinder, sandpaper, etc.), or chemical removal (e.g., by solvents such as acetone, alcohols, acids, etc.).
[0166] The coupler or fitting 640a includes a body 642a (e.g., a cylindrical body) defining an internal volume, the internal volume being configured to receive a portion of the axial end of the strength member 610a conductor 600a. For example, a predetermined length of the conductor layer 620a of the conductor 600a may be removed (e.g., a portion having a length within a range of about 150 mm (inclusive) to about 350 mm (inclusive) from the axial end of the conductor 600a). The cross-sectional width of the internal volume of the body 642a is less than the external cross-sectional width of the strength member 610a, so that inserting the axial end of the strength member 610a into the body 642a causes the inserted portion of the encapsulation layer 612a to be crimped. The sleeve 644a may be arranged around the body 642a (e.g., arranged circumferentially around the body 642a) and configured to contact the conductor layer 620a so as to electrically couple the coupler 640a to the conductor layer 620a. The coupler 640a may also include a connecting portion 646a defining a key hole 648a. The connecting portion 646a may be configured to couple to a corresponding hook or connector located on a pole (eg, a tensioning tower) from which the conductor 630a may be suspended.
[0167] As previously discussed, the composite material forming the core 612a may be susceptible to damage from compressive forces. However, the encapsulation layer 614a disposed about the core 612a also acts as a protective layer to protect the core 612a from the compressive forces applied during crimping of the body 642a about the strength member 610a. This advantageously enables conventional crimp fittings or couplers to be used with the conductor 600a, providing installation convenience and flexibility, and reducing costs. Although Fig. 6A A particular configuration of fitting or coupler 640a is depicted, but it should be appreciated that any crimp coupler may be used with conductor 600a or any other conductor described herein, including crimp couplers used to couple one conductor to another.
[0168] Conductor 600a is coated with coating 630a. In addition, coating 630a is also coated on at least a portion of fitting or coupler 640a. Coating 630a can be formulated to have a solar absorptivity of less than 0.5 (e.g., 0.49, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.1 (inclusive), or even lower) at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and / or a radiant emissivity greater than 0.5 (e.g., 0.51, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 (inclusive), or even higher) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive). For example, coating 630a can be formulated to have a radiant emissivity equal to or greater than 0.75 (e.g., 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95 (inclusive), or even higher) at an operating temperature of about 200°C at a wavelength of about 6 microns, and / or a solar absorptivity less than 0.3 (e.g., 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.15, 0.10 (inclusive), or even lower) at a wavelength of less than 2.5 microns. In some embodiments, the outer coating 630a can result in a reduction in the operating temperature of the conductor 630a and the fitting or coupler at a particular current within a range of about 5°C (inclusive) to about 40°C (inclusive) (e.g., 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 25, 30, 35, or 40°C (inclusive)), as described herein. The coating 630a can include the outer coating 130, 230, 330, 430, 530, or any other coating described herein. In some embodiments, the coupler 640a can be pre-coated with the coating 630a before coupling with the conductor 600a. In other embodiments, the coupler 640a can be coated with the coating 630a, for example, after the coupler 640a is coupled to the conductor 630a, to form a continuous coating from the conductor 630a to the coupler 640a.
[0169] Figure 6B6 is a schematic diagram of another fitting or coupler 640b according to an embodiment that can be used to splice a first conductor 600b1 to a second conductor 600b2 and is coated with a coating 630b having low solar absorptivity and high radiant emissivity. The first conductor 600b1 includes a first strength member 610b1 and a first conductor layer 620b1 disposed around the first strength member 610b1, the first strength member 610b1 including a first core 612b1 and a first encapsulation layer 614b1. Similarly, the second conductor 600b2 includes a second strength member 610b2 and a second conductor layer 620b1 disposed around the second strength member 610b1, the second strength member 610b2 including a second core 612b2 and a second encapsulation layer 614b2. The conductors 600b1 and 600b2 can be substantially similar to the conductor 600a and are not described in further detail herein. Each of the first conductor layer 620b1 and the second conductor layer 620b2 may also be coated with the coating 630a. Before coupling the coupler 640b to the conductors 600a and 600b, a portion of the coating 630a disposed at the respective axial ends of the conductor layers 620b1 and 620b2 inserted into the coupler 640b may be removed from the conductor layers 620b1 and 620b2, similar to the example described with respect to Fig. 6A The coupling of conductor 600a to coupler 640a is described in detail.
[0170] The coupler or fitting 640b includes a body 642b (e.g., a cylindrical body) defining an internal volume, the internal volume being configured to receive a portion of the corresponding axial ends of the first strength member 610b1 and the second strength member 600b2. For example, a predetermined length of the conductor layer 620b1 / b2 of the conductor 600b1 / b2 may be removed (e.g., a portion having a length ranging from about 150 mm (inclusive) to about 350 mm (inclusive) from the axial ends of the conductor 600b1 / b2). The cross-sectional width of the internal volume of the body 642b is smaller than the external cross-sectional width of the strength member 610b1 / b2, so that inserting the axial ends of the first strength member 610b1 and the second strength member 610b2 into the body 642b causes the inserted portions of the encapsulation layer 612b1 / b2 to be crimped and spliced to each other. The sleeve 644b may be disposed around the body 642b (eg, disposed circumferentially around the body 642b) and configured to contact the conductor layers 620b1 / b2 to electrically couple the coupler 640b to the conductor layers 620b1 / b2.
[0171] As previously described, the composite material forming the core 612b1 / b2 may be susceptible to damage by compression forces. However, the encapsulation layer 614b1 / b2 disposed around the core 612b1 / b2 also acts as a protective layer to protect the core 612b1 / b2 from the compressive forces applied during crimping of the body 642b1 / b2 around the strength member 610b1 / b2.
[0172] The conductor 600b1 / b2 is coated with a coating 630b. In addition, the coating 630b1 / b2 is also coated on at least a portion of the fitting or coupler 640b1 / b2. The coating 630b can be formulated to have a solar absorptivity of less than 0.5 (e.g., 0.49, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.1 (inclusive), or even lower) at a wavelength less than 2.5 microns at an operating temperature in the range of 60°C (inclusive) to 250°C (inclusive), and / or a radiant emissivity greater than 0.5 (e.g., 0.51, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 (inclusive), or even higher) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive). Coating 630b may be substantially similar to coating 630a and will not be described in detail herein. In some embodiments, coupler 640b may be pre-coated with coating 630b before coupling with conductors 600b1 and 600b2. In other embodiments, coupler 640b may be coated with coating 630b after coupler 640b is coupled to conductors 600b1 and 600b2, for example, to form a continuous coating from conductors 630b1 and 600b2 to coupler 640b.
[0173] Figure 7 7 is a schematic flow chart of a method 700 for reducing the solar absorptivity and increasing the radiant emissivity of a conductor by disposing a coating (e.g., outer coating 130, 230, 330, or 630) having low solar absorptivity and high radiant emissivity on a conductor layer of a conductor (e.g., conductor 100, 200, 300, 600) according to an embodiment, the conductor including a strength member (e.g., strength member 110, 210, 310, 610) and a conductor layer (e.g., conductor layer 120, 220, 320, 620). Although described with respect to conductor 100, it should be appreciated that the method can be used to form any composite conductor coated with an outer coating, as described herein.
[0174] The method 700 includes forming a strength member 110 at 702. The strength member 110 includes a core 112 formed of a composite material and an encapsulation layer 114, as previously described herein. The core 112 may include any suitable composite material and may be formed using any suitable method as described with respect to the conductor 100. The encapsulation layer 114 may be formed of Al, Cu, or any other suitable material as described herein. In addition, the encapsulation layer 114 may be arranged around the core 112 using a conformal machine or any other suitable method, as described with respect to the conductor 100.
[0175] In some embodiments, at 704, inner coating 116 may be disposed on the outer surface of encapsulation layer 114, for example, by brushing, spray coating, post-deposition cross-linking, shrink wrapping, any other suitable method, or a combination thereof. Inner coating 116 may be formulated to have a low absorptivity of less than 0.5 at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive) at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and may be formed of any suitable material, as described herein.
[0176] At 706, a set of conductive strands are arranged on the strength member 110 (e.g., around the encapsulation layer 114 or around the inner coating 116 arranged around the encapsulation layer 114) to form a conductor layer 120. The conductive strands can be formed of aluminum, aluminum alloys, copper, or copper alloys containing microalloys as conductive media, etc. In some embodiments, the conductor layer 120 may include conductive strands that include Z, C, or S wires to hold the outer strands in place. The conductor layer 120 may have any suitable cross-sectional shape, such as circular, triangular, trapezoidal, etc. In some embodiments, the conductor layer 120 may include a stranded aluminum layer that may be circular or trapezoidal aluminum strands. In some embodiments, the conductor layer 120 may include Z-shaped aluminum strands. In some embodiments, the conductor layer 120 may include S-shaped aluminum strands.
[0177] As described herein, a conformal machine or any suitable method may be used to arrange the conductive strands around the strength member 110. In some embodiments, the conductor layer 120 may include a first group of conductive strands arranged around the strength member 110 in a first winding direction (e.g., the strength member 110 is helically wound in a first rotational direction), a second group of conductive strands arranged around the first group of strands in a second winding direction (e.g., the first group of conductive strands are helically wound in a second rotational direction opposite the first rotational direction), and may also include a third group of strands wound around the second group of strands in the first winding direction.
[0178] In some embodiments, at 708 , an outer surface of the conductor layer 120 (eg, an outer surface of each conductive strand, or only the radially outer surfaces of the outermost conductive strands included in the conductor layer 120 ) is processed. In some embodiments, at 710 , an insulating layer 122 is disposed around the conductor layer 120 .
[0179] For example, the outer surface of the conductive strands of the conductor layer 120 can be cleaned using any suitable method, such as by acid, solvent, and / or textured using mechanical means (e.g., sandblasting), to facilitate adhesion of the outer coating 130 to the outer surface of the conductor layer 120. In some embodiments where the insulating layer 122 is disposed around the conductor layer 120, the outer surface of the insulating layer 122 can be cleaned or textured (e.g., by sandblasting).
[0180] At 712, an outer coating 130 is disposed around the conductor layer 120, or in embodiments where the insulating layer 122 is disposed around the conductor layer 120, the outer coating 130 is disposed around the insulating layer 122. The outer coating 130 may be disposed using any suitable method, for example, by brushing, spray coating, post-deposition cross-linking, shrink wrapping, any other suitable method, or combinations thereof. The outer coating 130 can be formulated to have a solar absorptivity of less than 0.5 (e.g., 0.49, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.15, 0.1 (inclusive), or even lower) at a wavelength less than 2.5 microns at an operating temperature in the range of 60° C. (inclusive) to 250° C. (inclusive), and a radiant emissivity greater than 0.5 (e.g., 0.51, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 (inclusive), or even higher) at a wavelength in the range of 2.5 microns (inclusive) to 15 microns (inclusive). For example, the outer coating 130 can be formulated to have a radiant emissivity equal to or greater than 0.75 (e.g., 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95 (inclusive), or even higher) at an operating temperature of about 200° C. at a wavelength of about 6 microns and a solar absorptivity less than 0.3 (e.g., 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.15, 0.10 (inclusive), or even lower) at a wavelength of less than 2.5 microns. In some embodiments, the outer coating 130 may be configured to cause a reduction in the operating temperature of the conductor 100 at a particular current within a range of about 5° C. (inclusive) to about 40° C. (inclusive) (e.g., 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 25, 30, 35, or 40° C. (inclusive)), as described herein. The outer coating 130 may include microstructures and nanopores and may be formed of any suitable material, as described herein. In some embodiments, the outer coating 130 may additionally or alternatively be formulated to have an erosion resistance that is at least 5% greater than the erosion resistance of aluminum or an aluminum alloy (e.g., an erosion resistance that is at least about 100% greater than the erosion resistance of aluminum or an aluminum alloy). In some embodiments, the outer coating 130 may have a Vickers hardness greater than 175 MPa.
[0181] In some embodiments, method 700 may also include, at 714, removing a portion of coating 130 (eg, outer coating) disposed proximate an axial end of the conductor. Fig. 6A and Figure 6BAs described above, any suitable physical or chemical means may be used to remove the portion of the outer coating 130. The method 700 may also include, at 716, removing a predetermined length of the conductor layer 120 from the axial end of the conductor 100 (e.g., by stripping or cutting the conductor layer 120) to expose the strength member 110 disposed below the conductor layer 120, as described with reference to FIG. Fig. 6A and Figure 6B The method 700 may also include, at 718, coupling a coupler (e.g., coupler 640b or 640b) to the axial end of the conductor 100, such as by crimping the coupler to the axial end of the strength member 110, as described above with respect to Fig. 6A and Figure 6B described.
[0182] example
[0183] The effects of the low solar absorptivity and high radiant emissivity coatings described herein on the operating temperature and current carrying capacity of the conductors described herein were simulated, and the results of the simulations are described in detail in the following examples. It should be appreciated that these examples are for illustration only and should not be construed as limiting the present disclosure.
[0184] Coatings having a solar absorptivity of less than 0.2 and a radiant emissivity of greater than 0.9 were arranged on the outer surfaces of various conductors and their effects on the operating temperature were analyzed. The results are shown in Table 1, where the symbol "TS" cited in the conductor type refers to a conductor according to the present disclosure (e.g., conductors 100, 200, 300, 600).
[0185] Table 1: Operating temperatures of various conductors with and without low solar absorptivity and high radiant emissivity coatings.
[0186]
[0187] As shown in Table 1, depositing a coating having low solar absorptivity and high radiant emissivity on the outer surface of a TS conductor can result in a reduction in the operating temperature of the conductor by at least 10° C., including a reduction in operating temperature of greater than 30° C. Thus, the TS conductor can be operated at a lower temperature while allowing the same current to be delivered through the TS conductor, or allowing a higher current to be delivered through the TS conductor at the same operating temperature.
[0188] Using various ACSR conductors as models, the performance of various TS conductors operating under environmental conditions of 30°C, 2 ft / sec wind speed at 90 degrees to the conductor, and 900 ft above sea level was simulated to determine the increase in current carrying capacity or reduction in operating current when using the outer coating as described herein. The results are summarized in Table 2.
[0189] Table 2. Effect of low solar absorptivity and high radiant emissivity coatings on the current carrying capacity and operating temperature of various TS conductors. A = current carrying capacity; OT = operating temperature; SA = solar absorptivity; RE = radiant emissivity.
[0190]
[0191]
[0192] As observed in Table 2, the greatest reduction in operating temperature or improvement in ampacity is observed with an outer coating having a solar absorptivity of 0.2 and a radiative emissivity of 0.9. The effect of the higher emissivity (225A vs. 254A improvement at 200°C; 104A vs. 121A improvement at 90°C) may be less significant in windier conditions (4' / s vs. 2' / s) as convective heat losses become more significant. The effect of reduced solar absorptivity (25A vs. 29A at 200°C; 53A vs. 61A at 90°C) may also be less significant, while minimizing absorptivity is more important at lower temperature operation because radiative cooling is not as dominant at lower temperatures (radiative losses are proportional to the fourth power of temperature).
[0193] As used herein, the singular forms "a", "an", and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, the term "member" is intended to mean a single member or a combination of members, and "material" is intended to mean one or more materials, or a combination thereof.
[0194] As used herein, the terms "about" and "approximately" generally mean ±10% of the stated value. For example, about 0.5 will include 0.45 and 0.55, about 10 will include 9-11, and about 1000 will include 900-1100.
[0195] The terms "substantially" and similar terms utilized herein are intended to have a broad meaning consistent with common and accepted usage by those of ordinary skill in the art to which the subject matter of the present disclosure belongs. For example, the term "substantially flat" means that there may be slight surface variations or undulations due to manufacturing variations that exist on an otherwise flat surface. It should be understood by those skilled in the art reviewing this disclosure that these terms are intended to allow description of certain features described and claimed without limiting the scope of those features to the precise arrangements and / or numerical ranges provided. Thus, these terms should be understood to indicate that non-substantial or inconsequential modifications or alterations of the subject matter described and claimed are considered to be within the scope of the invention as set forth in the appended claims.
[0196] As used herein, the term "coupled" and the like means that two components are joined directly or indirectly to one another. Such connection may be fixed (e.g., permanent) or movable (e.g., removable or releasable). Such connection may be achieved by the two components or the two components and any additional intermediate components being integrally formed as a single unitary body with one another, or by the two components or the two components and any additional intermediate components being attached to one another.
[0197] It is important to note that the structure and arrangement of the various exemplary embodiments are merely illustrative. Although only a few embodiments are described in detail in this disclosure, those skilled in the art who review this disclosure will readily appreciate that many modifications are possible (e.g., the size, dimensions, structure, shape, and proportions of the various elements, parameter values, mounting arrangements, use of materials, colors, orientations, etc.) without substantially departing from the novel teachings and advantages of the subject matter described herein. Other substitutions, modifications, changes, and omissions may also be made in the design, operating conditions, and arrangement of the various exemplary embodiments without departing from the scope of the present invention.
[0198] Although this specification contains many specific implementation details, these details should not be understood as limitations on the scope of any invention or what may be claimed, but rather should be understood as descriptions of features that are unique to a particular implementation of a particular invention. Certain features described in this specification in the context of separate implementations may also be implemented in combination in a single implementation. Conversely, the individual features described in the context of a single implementation may also be implemented in multiple implementations, either individually or in any suitable sub-combination. In addition, although features may be described above as functioning in certain combinations, or even initially claimed as such, in some cases, one or more features in the claimed combination may be deleted from the combination, and the claimed combination may refer to a sub-combination or a variant of a sub-combination.
[0199] Thus, specific implementations of the present invention have been described. Other implementations are within the scope of the following claims. In some cases, the actions recited in the claims can be performed in a different order and still achieve the desired results. In addition, the processes described in the accompanying drawings do not necessarily require the specific order or sequential order shown to achieve the desired results. In some implementations, multitasking and parallel processing may be advantageous.
Claims
1. A device comprising: A strength member, the strength member comprising: a core formed of a composite material, and an encapsulation layer disposed around the core; a conductor layer disposed around the strength member; and A coating is arranged on the conductor layer, the coating being formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns at an operating temperature in the range of 60°C to 250°C, and a radiant emissivity of greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns.
2. The device of claim 1, wherein the coating is formulated to have a radiant emissivity equal to or greater than 0.75 at a wavelength of about 6 microns and a solar absorptivity less than 0.3 at a wavelength less than 2.5 microns at an operating temperature of about 200°C.
3. The device according to claim 1 or 2, wherein the coating comprises: microstructures having a size in the range of 3 micrometers to 15 micrometers, the microstructures being configured so that the coating has a radiation emissivity greater than 0.5; and The nanopores have a size in the range of 50 nm to 700 nm, and the nanostructures are configured to allow the coating to have a solar absorptivity in the range of less than 0.
5.
4. The device according to claim 3, wherein the coating comprises a fluoropolymer and / or a polyurethane.
5. The device of claim 3, wherein the microstructure comprises at least one of a metal oxide, a metal nitride, a metal fluoride, a metal carbide, a metal carbonate, or a rare earth element.
6. The device of claim 5, wherein the microstructure comprises carbonate.
7. The device according to claim 1 or 2, wherein the coating comprises: a first layer disposed on the conductor layer, the first layer having a radiation emissivity greater than 0.5; and A second layer is disposed above the first layer, the second layer having a solar absorptivity less than 0.
5.
8. The device according to any one of claims 1, 2, 3 or 7, wherein the device further comprises: An inner coating layer disposed between the encapsulation layer and the conductor layer, the inner coating layer being formulated to have a heat absorption rate of less than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60° C. to 250° C.
9. The apparatus of any one of claims 1, 2, 3 or 7, wherein the conductor layer comprises a plurality of conductive strands arranged around the strength member.
10. The device of any one of claims 1, 2, 3 or 7, wherein the coating is formulated to have a corrosion resistance at least 5% greater than the corrosion resistance of aluminum or an aluminum alloy.
11. The device of any one of claims 1, 2, 3 or 7, wherein the coating is hydrophilic.
12. An apparatus comprising: A strength member, the strength member comprising: a core formed of a composite material, and An encapsulation layer is arranged around the core, and an outer surface of the encapsulation layer is configured to have a reflectivity greater than 50% at a thermal radiation wavelength corresponding to an operating temperature greater than 90°C.
13. The device of claim 12, wherein an outer surface of the encapsulation layer is treated to have a reflectivity greater than 50%.
14. A device according to claim 12 or 13, wherein the outer surface is coated with a coating having a reflectivity greater than 50%.
15. The device according to claim 12 or 13, further comprising: A conductor layer is disposed around the strength member.
16. A device according to claim 15, wherein a coating is arranged on the conductor layer, and the coating is formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns at an operating temperature in the range of 60°C to 250°C, and a radiation emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns.
17. The device of claim 16, wherein the coating is formulated to have a radiant emissivity equal to or greater than 0.75 at a wavelength of about 6 microns and a solar absorptivity less than 0.3 at a wavelength less than 2.5 microns at an operating temperature of about 200°C.
18. The device of claim 16, wherein the coating comprises: microstructures having a size in the range of 3 micrometers to 15 micrometers, the microstructures being configured so that the coating has a radiation emissivity greater than 0.5; and The nanopores have a size in the range of 50 nm to 700 nm, and the nanostructures are configured to allow the coating to have a solar absorptivity in the range of less than 0.
5.
19. The device of claim 15, wherein the coating comprises a fluoropolymer and / or a polyurethane.
20. The device of claim 15 or 16, wherein the microstructure comprises at least one of a metal oxide, a metal nitride, a metal fluoride, a metal carbide, a metal carbonate, or a rare earth element.
21. The device of claim 17, wherein the microstructure comprises carbonate.
22. An apparatus comprising: A strength member, the strength member comprising: a core formed of a composite material, and an encapsulation layer disposed around the core; a conductor layer disposed around the strength member; and A coating is disposed on the conductor layer, the coating being formulated to have a corrosion resistance at least 5% greater than the corrosion resistance of aluminum or an aluminum alloy.
23. The device of claim 22, wherein the coating has a corrosion resistance at least about 100% greater than the corrosion resistance of aluminum or an aluminum alloy.
24. A device according to claim 22 or 23, wherein the coating has a Vickers hardness greater than 175 MPa.
25. A device according to any one of claims 22, 23 or 24, wherein the coating is also formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns and a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60°C to 250°C.
26. An assembly comprising: A conductor, the conductor comprising: A strength member, the strength member comprising: a core formed of a composite material, and an encapsulation layer disposed around the core; a conductor layer disposed around the strength member; a coupler coupled to an axial end of the conductor; and A coating arranged on an outer surface of the coupler, the coating being formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns and / or a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60°C to 250°C.
27. The assembly of claim 26, wherein the coating is a first coating, the assembly further comprising: A second coating disposed on at least a portion of the outer surface of the conductor layer of the conductor, the coating being formulated to have a solar absorptivity of less than 0.5 at a wavelength less than 2.5 microns and / or a radiant emissivity greater than 0.5 at a wavelength in the range of 2.5 microns to 15 microns at an operating temperature in the range of 60°C to 250°C.
28. The assembly of claim 27, wherein said second coating is disposed on a portion of said conductor layer that is axially disposed outside of said coupler.
29. An assembly according to any one of claims 26, 27 or 28, wherein said coupler is crimped to said axial end of said conductor.
30. The assembly of claim 29, wherein a predetermined length of conductor layer at the axial end of the conductor is removed prior to coupling the coupler to the conductor such that the coupler is crimped to the strength member.
Citation Information
Patent Citations
Energy efficient conductors with reduced thermal knee points and the method of manufacture thereof
US9633766B2
Cited By
Graphene-reinforced heavy-duty epoxy coating for marine environment
CN121160180A
Method for micro-arc oxidation of ceramic membrane on basis of t-ZrO2 reinforced aluminum alloy drill rod
CN121653796A